Laminate and organic el display device

By using a laminated body with a specific structure in an organic EL display device, the problem of changing the color tone of white display during long outdoor use is solved, and the stability of the color tone and ultraviolet protection are achieved.

CN119731566APending Publication Date: 2025-03-28SUMITOMO CHEM CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380060022.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-05-24
Filing Date
2023-06-09
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The organic EL display device used outdoors for a long time is prone to change in the tone of the luminous color when displayed in white.

Method used

A laminate consisting of a first ultraviolet absorbing layer, a first light absorption anisotropic layer, a second ultraviolet absorbing layer and a second light absorption anisotropic layer is used to ensure that these layers meet a specific transmittance and absorbance relationship to suppress the influence of ultraviolet rays.

Benefits of technology

Even when exposed to outdoors for a long time, the laminate can effectively suppress the change in the luminous color tone during white display, and protect the display device from deterioration of ultraviolet rays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731566A_ABST
    Figure CN119731566A_ABST
Patent Text Reader

Abstract

[Problem] To provide a laminate capable of suppressing a change in color tone when a user intensively feels white display (light emission color) even when exposed to the outside for a long period of time. [Solution] A laminate has a first ultraviolet-absorbing layer, a first light-absorbing anisotropic layer, a second ultraviolet-absorbing layer, and a second light-absorbing anisotropic layer in this order. The first light-absorbing anisotropic layer is formed from a composition containing one or more dichroic pigments and a liquid crystalline compound, and the second light-absorbing anisotropic layer has an absorption axis in a horizontal direction with respect to the plane of the second light-absorbing anisotropic layer. The first ultraviolet-absorbing layer and the second ultraviolet-absorbing layer satisfy the relationship represented by formula (1), and the first light-absorbing anisotropic layer satisfies the relationship represented by formula (2). T (380) < = 20 (1), Azgt; (Ax + Ay) / 2 (2) [In formula (1), T (380) represents transmittance [%] at a wavelength of 380 nm. In formula (2), Ax, Ay, and Az are the absorbance of the first light-absorbing anisotropic layer at the maximum absorption wavelength in the wavelength range of 410 nm to 780 nm, and represent the absorbance of linearly polarized light that oscillates in the x-axis direction, the y-axis direction, and the z-axis direction, respectively. The x-axis is a direction parallel to the absorption axis direction of the second light-absorbing anisotropic layer in the plane of the first light-absorbing anisotropic layer, the y-axis is a direction orthogonal to the x-axis in the plane of the first light-absorbing anisotropic layer, and the z-axis is a direction orthogonal to the x-axis and the y-axis. ].
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminate and an organic EL display device. Background Art

[0002] In an organic EL (electroluminescent) display device, in order to reduce the hue difference between the front hue when viewed from the front and the oblique hue when viewed from an oblique direction when displaying white, it is known to use a stack having a vertically oriented liquid crystal cured film containing a dichroic pigment and a horizontally oriented phase difference film (for example, Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2020-76920 Summary of the invention

[0006] Problems to be solved by the invention

[0007] When an organic EL display device including the above-mentioned laminated body is used outdoors for a long period of time, a change in the color tone of white display (luminescent color) may be strongly felt.

[0008] An object of the present invention is to provide a laminated body capable of suppressing a change in color tone (luminescent color) when white display is strongly felt even when the laminated body is exposed outdoors for a long period of time, and an organic EL display device including the laminated body.

[0009] Means for solving problems

[0010] The present invention provides the following laminated body and organic EL display device.

[0011] [1] A laminate comprising, in this order, a first ultraviolet absorbing layer, a first light absorbing anisotropic layer, a second ultraviolet absorbing layer, and a second light absorbing anisotropic layer,

[0012] The first light absorption anisotropic layer is formed of a composition containing one or more dichroic pigments and a liquid crystal compound.

[0013] The second light absorption anisotropic layer has an absorption axis in a direction parallel to the plane thereof.

[0014] The first ultraviolet absorbing layer and the second ultraviolet absorbing layer both satisfy the relationship of the following formula (1):

[0015] The first light absorption anisotropic layer satisfies the relationship of the following formula (2).

[0016] T(380)≤20 (1)

[0017] Az>(Ax+Ay) / 2 (2)

[0018] [In formula (1), T(380) represents the transmittance [%] at a wavelength of 380 nm.

[0019] In formula (2), Ax, Ay and Az are the absorbances of the maximum absorption wavelength of the aforementioned first light absorption anisotropic layer in the wavelength range of not less than 410 nm and not more than 780 nm, and respectively represent the absorbances of linearly polarized light vibrating along the x-axis direction, the y-axis direction and the z-axis direction.

[0020] The x-axis is a direction parallel to the absorption axis direction of the second light absorption anisotropic layer in the plane of the first light absorption anisotropic layer.

[0021] The y-axis is a direction orthogonal to the x-axis in the plane of the first light-absorbing anisotropic layer.

[0022] The aforementioned z-axis is a direction orthogonal to the aforementioned x-axis and the aforementioned y-axis.]

[0023] [2] The laminate according to [1], wherein at least one of the first ultraviolet absorbing layer and the second ultraviolet absorbing layer satisfies the relationship of the following formula (3).

[0024] T(410)≤20 (3)

[0025] [In formula (3), T(410) represents the transmittance [%] at a wavelength of 410 nm.]

[0026] [3] The laminate according to [2], wherein the second ultraviolet absorbing layer satisfies the relationship of the above formula (3).

[0027] [4] The laminate according to any one of [1] to [3], wherein the liquid crystal compound can form a smectic liquid crystal phase.

[0028] [5] A laminate as described in any one of [1] to [4], further comprising a phase difference layer satisfying the relationship of the following formulae (4) and (5) on the side of the second light absorption anisotropic layer opposite to the second ultraviolet absorption layer side,

[0029] The retardation layer is a cured layer of a polymerizable liquid crystal compound.

[0030] 120nm≤ReA(550)≤160nm (4)

[0031] ReA(450) / ReA(550)≤1.0 (5)

[0032] [In formula (4) and formula (5), ReA(λ) represents the in-plane retardation value of the retardation layer at a wavelength of λ [nm].]

[0033] [6] The laminate according to [5], wherein the retardation layer satisfies the relationship of the following formula (6).

[0034] TA(380)≤20 (6)

[0035] [In formula (6), TA(380) represents the transmittance [%] of the retardation layer at a wavelength of 380 nm.]

[0036] [7] The laminate according to any one of [1] to [6], wherein the dichroic dye is an azo compound.

[0037] [8] The laminate according to any one of [1] to [7], wherein the first light absorption anisotropic layer satisfies the relationship between the following formulas (7) and (8).

[0038] Ax(z=60°) / Ax≥5 (7)

[0039] Ay(z=60°) / Ay≥5 (8)

[0040] [In formula (7), Ax(z=60°) is the absorbance of the aforementioned maximum absorption wavelength of the aforementioned first light absorption anisotropic layer, and represents the absorbance of linearly polarized light vibrating along the aforementioned x-axis direction when the aforementioned first light absorption anisotropic layer is rotated 60° with the aforementioned y-axis as the rotation axis.

[0041] In formula (8), Ay(z=60°) is the absorbance of the maximum absorption wavelength of the first light absorption anisotropic layer, and represents the absorbance of linearly polarized light vibrating along the y-axis direction when the first light absorption anisotropic layer is rotated 60° with the x-axis as the rotation axis.]

[0042] [9] The laminate according to any one of [1] to [8], wherein the second ultraviolet absorbing layer satisfies the relationship of the following formula (9).

[0043] 80nm≤ReB(550)≤160nm (9)

[0044] [In formula (9), ReB(550) represents the in-plane retardation value of the second ultraviolet absorbing layer at a wavelength of 550 nm.]

[0045]

[10] An organic EL display device, wherein the laminate according to any one of [1] to [9] is laminated on a display element via a pressure-sensitive adhesive layer.

[0046] Effects of the Invention

[0047] According to the present invention, it is possible to provide a laminated body capable of suppressing a change in color tone (luminescent color) when white display is strongly felt even when the laminated body is exposed outdoors for a long period of time. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] [ Figure 1 ] is a cross-sectional view schematically showing a stacked body involved in one embodiment of the present invention.

[0049] [ Figure 2 ] is a cross-sectional view schematically showing a stacked body according to another embodiment of the present invention. DETAILED DESCRIPTION

[0050] Hereinafter, preferred embodiments of the laminate and the organic EL display device will be described with reference to the drawings.

[0051] (Laminated body)

[0052] Figure 1 and Figure 2 Schematically shows a cross-sectional view of a laminated body according to one embodiment of the present invention. Figure 1 and Figure 2 As shown, the laminated bodies 1 and 2 have the first ultraviolet absorbing layer 21 (hereinafter, sometimes referred to as the "first UV absorbing layer 21"), the first light absorbing anisotropic layer 11, the second ultraviolet absorbing layer 22 (hereinafter, sometimes referred to as the "second UV absorbing layer 22"), and the second light absorbing anisotropic layer 12 in this order. In the laminated bodies 1 and 2, usually, the first UV absorbing layer 21 side becomes the viewing side.

[0053] like Figure 2 As shown, the laminate 2 may include a phase difference body 13 including one or more phase difference layers on the side of the second light absorption anisotropic layer 12 opposite to the second UV absorbing layer 22. In the laminate 2, the second light absorption anisotropic layer 12 and the phase difference body 13 may constitute an antireflection film functioning as an elliptically polarizing plate.

[0054] The first light absorption anisotropic layer 11 is formed of a composition containing one or more dichroic pigments and a liquid crystal compound (hereinafter, sometimes referred to as "the first composition"), and satisfies the relationship of the following formula (2). The second light absorption anisotropic layer 12 has an absorption axis in a direction horizontal to its plane. In the laminates 1 and 2, the first UV absorption layer 21 and the second UV absorption layer 22 both satisfy the relationship of the following formula (1).

[0055] T(380)≤20 (1)

[0056] Az>(Ax+Ay) / 2 (2)

[0057] [In formula (1), T(380) represents the transmittance [%] at a wavelength of 380 nm.

[0058] In formula (2), Ax, Ay and Az are the absorbances of the first light absorption anisotropic layer 11 at the maximum absorption wavelength within the wavelength range of 410 nm to 780 nm, and respectively represent the absorbances of linearly polarized light vibrating along the x-axis direction, the y-axis direction and the z-axis direction.

[0059] Here, the x-axis is a direction parallel to the absorption axis direction of the second light absorption anisotropic layer 12 in the plane of the first light absorption anisotropic layer 11.

[0060] The y-axis is a direction perpendicular to the x-axis in the plane of the first light-absorbing anisotropic layer 11, and the z-axis is a direction perpendicular to the x-axis and the y-axis.]

[0061] The laminates 1 and 2 have a first UV absorbing layer 21 and a second UV absorbing layer 22 that satisfy formula (1). Since the first UV absorbing layer 21 and the second UV absorbing layer 22 are provided, the layer located on the lower side (the side opposite to the viewing side) of these layers can be protected from ultraviolet rays even when exposed to the outdoors for a long time. Therefore, it is believed that when the laminates 1 and 2 are exposed to the outdoors for a long time, when the display device using the laminates 1 and 2 displays white (luminous color), the hue change such as the change from the initial hue and the hue difference between the hue in the front direction and the hue in the oblique direction can be strongly felt. The laminates 1 and 2 can also suppress the hue feeling when the black display is exposed to the outdoors for a long time from changing significantly compared to the hue feeling when the black display is displayed at the beginning.

[0062] It is preferred that at least one of the first UV absorbing layer 21 and the second UV absorbing layer 22 satisfy the relationship of the following formula (3), and it is more preferred that the second UV absorbing layer 22 satisfy the relationship of the following formula (3).

[0063] T(410)≤20 (3)

[0064] [In formula (3), T(410) represents the transmittance [%] at a wavelength of 410 nm.]

[0065] By making at least one of the first UV absorbing layer 21 and the second UV absorbing layer 22 satisfy the relationship of the above formula (3), it is easy to reduce the influence caused by ultraviolet rays, especially near ultraviolet rays. As a result, it is easy to further suppress the strong feeling of color tone change when the display device displays white when the stacked bodies 1 and 2 are exposed to the outdoors for a long time. It is easy to further suppress the color tone feeling when the stacked bodies 1 and 2 are exposed to the outdoors for a long time. Compared with the initial black display, the color tone feeling changes significantly. In addition, when the stacked bodies 1 and 2 are applied to the display device, the light-emitting layer included in the display device can also be protected from the influence of near ultraviolet rays, and therefore, the light-emitting layer that is easily degraded by near ultraviolet rays can also be protected.

[0066] When comparing the case [i] where the first UV absorbing layer 21 does not satisfy the relationship of the above formula (3) and the second UV absorbing layer 22 satisfies the relationship of the above formula (3) with the case [ii] where the first UV absorbing layer 21 satisfies the relationship of the above formula (3) and the second UV absorbing layer 22 does not satisfy the relationship of the above formula (3), it is inferred that in the case [i], it is easier to suppress the change in color tone when the stacked bodies 1 and 2 are exposed to the outdoors for a long time, when the white display of the display device is displayed. When comparing the layer that satisfies only the relationship of the above formula (1) and the layer that satisfies the relationship of the above formula (1) and (3), there is a tendency that the ultraviolet absorption ability of the layer that satisfies the relationship of the above formula (1) and (3) is more likely to deteriorate when exposed to the outdoors for a long time. In addition, the first UV absorbing layer 21 is arranged relatively on the viewing side relative to the second UV absorbing layer 22. Therefore, when the laminates 1 and 2 are exposed outdoors for a long time, the second UV absorbing layer 22 is less susceptible to ultraviolet rays than the first UV absorbing layer 21, and degradation of ultraviolet absorption capability is easily suppressed. Therefore, it is preferred that at least the second UV absorbing layer 22 satisfies the relationship of the above formula (3).

[0067] The first UV absorbing layer 21 and the first light absorbing anisotropic layer 11 may be stacked in direct contact with each other, or another layer such as a first orientation layer (described later) may be interposed between the first UV absorbing layer 21 and the first light absorbing anisotropic layer 11 .

[0068] The first light absorption anisotropic layer 11 and the second UV absorption layer 22 may be stacked in direct contact with each other, or other layers such as a first orientation layer (described later) and a bonding layer (adhesive layer or pressure-sensitive adhesive layer) may be interposed between the first light absorption anisotropic layer 11 and the second UV absorption layer 22 .

[0069] The second UV absorbing layer 22 and the second light absorbing anisotropic layer 12 may be stacked in direct contact with each other, or other layers such as a second orientation layer (described later) and a bonding layer (adhesive layer or pressure-sensitive adhesive layer) may be interposed between the second UV absorbing layer 22 and the second light absorbing anisotropic layer 12 .

[0070] The stacked bodies 1 and 2 may have a first orientation layer for controlling the orientation of the liquid crystal compound. When the stacked bodies 1 and 2 have the first light absorption anisotropic layer 11 and the first orientation layer, the first light absorption anisotropic layer 11 and the first orientation layer are usually directly in contact with each other. The first orientation layer may be provided between the first UV absorption layer 21 and the first light absorption anisotropic layer 11, or between the first light absorption anisotropic layer 11 and the second UV absorption layer 22.

[0071] The stacked bodies 1 and 2 may have a second orientation layer for controlling the orientation of the liquid crystal compound. When the stacked bodies 1 and 2 have the second light absorption anisotropic layer 12 and the second orientation layer, the second light absorption anisotropic layer 12 and the second orientation layer are usually directly in contact. The second orientation layer may be provided between the second UV absorption layer 22 and the second light absorption anisotropic layer 12, or may be provided on the side of the second light absorption anisotropic layer 12 opposite to the second UV absorption layer 22 side.

[0072] The laminates 1 and 2 preferably have a layer structure of hard coating layer / transparent resin film / first light absorption anisotropic layer / laminating layer / transparent resin film / second light absorption anisotropic layer. The first UV absorption layer 21 is preferably a hard coating layer and / or a transparent resin film. The second UV absorption layer 22 is preferably a laminating layer and / or a transparent resin film. Preferably, the first UV absorption layer 21 and the second UV absorption layer are each independently a hard coating layer or a transparent resin film.

[0073] Hereinafter, each layer included in the laminated bodies 1 and 2 will be described in detail.

[0074] (First UV Absorption Layer (First Ultraviolet Absorption Layer))

[0075] The first UV absorbing layer 21 satisfies the relationship of the above formula (1). T(380) of the first UV absorbing layer 21 is 20% or less, 15% or less, 10% or less, 8% or less, or 5% or less, and is usually 0.01% or more.

[0076] The first UV absorbing layer 21 may satisfy the relationship of the above formula (3). When the second UV absorbing layer 22 does not satisfy the relationship of the above formula (3), it is preferred that the relationship of the above formula (3) is satisfied. T(410) of the first UV absorbing layer 21 may be 90% or less, 50% or less, 20% or less, 18% or less, or 15% or less, and is usually 0.01% or more. T(380) and T(410) of the first UV absorbing layer 21 may be measured as transmittances at wavelengths of 380 nm and 410 nm, respectively, using a spectrophotometer.

[0077] The first UV absorbing layer 21 preferably also satisfies the relationship of T(410) / T(450)≤0.9, more preferably satisfies the relationship of T(410) / T(450)≤0.5, and further preferably satisfies the relationship of T(410) / T(450)≤0.2. In the case where the second UV absorbing layer 22 does not satisfy this relationship, it is preferably satisfied in the first UV absorbing layer 21. By satisfying this relationship, light with a wavelength of less than 410 nm is absorbed, and on the other hand, light in the visible light region is not easily absorbed. Therefore, when assembled in a display device, a laminate can be provided that suppresses degradation caused by ultraviolet light and is not easily hindered from good color presentation. It should be noted that T(450) represents the transmittance [%] at a wavelength of 450 nm, and can be measured as the transmittance at a wavelength of 450 nm using a spectrophotometer.

[0078] The first UV absorbing layer 21 may be a single-layer structure or a multi-layer structure. When the first UV absorbing layer 21 is a single-layer structure, the first UV absorbing layer 21 is preferably a layer containing an ultraviolet absorber. When the first UV absorbing layer 21 has a multi-layer structure, at least one layer may have ultraviolet absorption capability, and preferably at least one layer containing an ultraviolet absorber is included. As the ultraviolet absorber contained in the first UV absorbing layer, a known ultraviolet absorber can be used.

[0079] As known ultraviolet absorbers, they can be roughly divided into inorganic ultraviolet absorbers and organic ultraviolet absorbers. The inorganic ultraviolet absorbers have good durability such as light resistance and heat resistance, but on the other hand, they tend to be poor in terms of control of absorption wavelength and compatibility with organic materials. On the other hand, organic ultraviolet absorbers are inferior to inorganic ultraviolet absorbers in terms of durability, but they are preferred because they can achieve control of absorption wavelength and compatibility with organic materials due to the freedom of molecular structure. As organic ultraviolet absorbers, for example, compounds containing benzophenone skeletons, triazole skeletons, triazine skeletons, cyanoacrylate skeletons, merocyanine skeletons, etc. can be cited. However, most of the organic ultraviolet absorbers with the above skeletons have a maximum absorption wavelength (λmax) below 360nm, so they cannot efficiently absorb the ultraviolet to near-ultraviolet region of 380 to 400nm. In order to fully absorb the light in this region, it is necessary to make the usage amount very large. Furthermore, many compounds having a skeleton capable of absorbing light having a wavelength of 380 nm or longer tend to color a composition containing an ultraviolet absorber or to easily deteriorate in a light resistance test, and this tendency becomes prominent particularly when oxygen is easily supplied.

[0080] As one embodiment of the ultraviolet absorber, there is mentioned a compound represented by the following formula (i) (hereinafter, sometimes referred to as “compound (i)”).

[0081] [Chemical formula 1]

[0082]

[0083] In the above formula (i), A represents a methylene group, a secondary amino group, an oxygen atom or a sulfur atom. From the viewpoint of exhibiting high light selective absorption, A preferably represents a methylene group, a secondary amino group or an oxygen atom.

[0084] In the above formula (i), R 1 represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. From the viewpoint of exhibiting high light selective absorption, R 1 It preferably represents an alkyl group having 1 to 8 carbon atoms, more preferably represents an alkyl group having 1 to 5 carbon atoms, and further preferably represents an alkyl group having 1 to 3 carbon atoms. Here, when the alkyl group has at least one methylene group, at least one of the methylene groups may be replaced by an oxygen atom or a sulfur atom. Examples of the alkyl group include methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, n-hexyl, n-octyl, n-decyl, methoxy, ethoxy, and isopropoxy.

[0085] In the above formula (i), R 2 and R 3Each independently represents a hydrogen atom or an alkyl group having 1 to 12 carbon atoms. From the viewpoint of exhibiting high light selective absorption, R 2 and R 3 Each independently represents preferably a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, more preferably a hydrogen atom or an alkyl group having 1 to 8 carbon atoms, further preferably a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and particularly preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms.

[0086] In the above formula (i), R 4 It represents an alkyl group having 3 to 50 carbon atoms, or an alkyl group having 3 to 50 carbon atoms having at least one methylene group, wherein at least one of the methylene groups is replaced by an oxygen atom.

[0087] Just R 4 In terms of the alkyl group having 3 to 50 carbon atoms, the number of carbon atoms is preferably 8 to 45 (e.g., 10 to 45), more preferably 12 to 40, further preferably 13 to 35, and particularly preferably 14 to 30, from the viewpoint of affinity with hydrophobic substances, solubility in hydrophobic solvents, and economic efficiency in production. It should be noted that a substituent may be bonded to a carbon atom on the alkyl group.

[0088] Just R 4 In terms of the alkyl group with 3 to 50 carbon atoms having at least one methylene group, the alkyl group with 3 to 40 carbon atoms, more preferably 4 to 35 carbon atoms, and particularly preferably 5 to 30 carbon atoms is preferably used from the viewpoint of affinity with hydrophobic substances, solubility in hydrophobic solvents, and economic efficiency in production. Here, in the alkyl group with 3 to 50 carbon atoms having at least one methylene group, at least one of the methylene groups is replaced by an oxygen atom, and examples thereof include ethoxy, propoxy, and 2-methoxyethoxymethyl. In addition, polyethylene glycol groups such as diethylene glycol groups and triethylene glycol groups, and polypropylene glycols such as dipropylene glycol groups and tripropylene glycol groups, etc. can also be mentioned.

[0089] In addition, in R 4 A substituent may be bonded to a carbon atom on the alkyl group. Examples of the substituent include a halogen atom, an alkyl group having 1 to 6 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 6 carbon atoms, an alkylsulfonyl group having 1 to 6 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkylthio group having 1 to 6 carbon atoms, an N-alkylamino group having 1 to 6 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 6 carbon atoms, and an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms.

[0090] In R 4In the case of an alkyl group having 3 to 50 carbon atoms, from the viewpoint of affinity with a hydrophobic substance and solubility in a hydrophobic solvent, R 4 More preferably, it is an alkyl group having 3 to 12 carbon atoms and having a branched structure, and still more preferably, it is an alkyl group having 6 to 10 carbon atoms and having a branched structure.

[0091] Here, the alkyl group having a branched structure refers to an alkyl group in which at least one of the carbon atoms in the alkyl group is a tertiary carbon or a quaternary carbon. Specific examples of the alkyl group having a branched structure having 3 to 12 carbon atoms include alkyl groups having the following structures.

[0092] [Chemical formula 2]

[0093]

[0094] [Wherein, * represents a connecting part.]

[0095] In the above formula (i), X 1 represents an electron-withdrawing group. From the viewpoint of improving the light selective absorption, X 1 Preferred are -NO2, -CN, -COR 8 、-COOR 9 、-OR 10 , halogen atoms (-F, -Cl, -Br, -I), -CSR 11 ,-CSOR 12 , or -CSNR 13 R 14 , more preferably nitro, cyano or -COOR 9 , more preferably cyano or -COOR 9 Here, R 8 , R 9 , R 10 , R 11 , R 12 , R 13 and R 14 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, for example, 2 to 5 carbon atoms, or a phenyl group.

[0096] In the above formula (i), Y 1 Indicates -CO-, -COO-, -OCO-, -O-, -S-, -NR 5 -、-NR 6 CO-、-CONR 7 -, or -CS-, preferably represents -CO-, -COO-, -OCO-, or -O-, and more preferably represents -CO-, -COO-, or -OCO-, from the viewpoint of improving light selective absorption. 5 , R 6and R 7 Each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, for example, 2 to 5 carbon atoms, or a phenyl group.

[0097] From the viewpoint of excellent solubility in various solvents and / or affinity with various compounds, compound (i) is preferably a compound represented by the following formula (i-1) (hereinafter, sometimes referred to as "compound (i-1)").

[0098] [Chemical formula 3]

[0099]

[0100] In the above formula (i-1), R 4-1 The alkyl group represents an alkyl group having 1 to 6 carbon atoms, preferably an alkyl group having 2 to 5 carbon atoms, and more preferably an alkyl group having 3 or 4 carbon atoms.

[0101] n represents an integer of 1 to 10, and from the viewpoint of excellent solubility in various solvents and / or affinity with various compounds, it is preferably an integer of 1 to 8, more preferably an integer of 1 to 6, for example, an integer of 1 to 4, and particularly an integer of 1 to 3. It should be noted that if n is within the above range, the light absorptivity per 1 mass part is improved, and even if the compound (i-1) contained in the first UV absorbing layer 21 and the second UV absorbing layer 22 (described later) is a small amount, it is possible to exhibit, for example, a blue light cutoff function, and in addition, when the compound (i-1) is contained in the resin film or coating layer described later, it is not easy to hinder their optical functions. In addition, when the compound (i-1) is contained in the adhesive layer as a bonding layer, it is not easy to hinder the bonding function.

[0102] In the above formula (i-1), A and R 1 , R 2 and R 3 It has the same meaning as described in the above formula (i).

[0103] The compound (i-1) is preferably a compound represented by the following formula (i-2) (hereinafter, sometimes referred to as "compound (i-2)").

[0104] [Chemical formula 4]

[0105]

[0106] By replacing compound (i-1) with compound (i-2), the solubility in various solvents and / or the affinity with various compounds are excellent, so that it becomes easy to dissolve the compound uniformly in the solvent. In addition, at the same time, the affinity with various compounds is also excellent, showing amphiphilicity. Therefore, when compound (i-2) is contained in the first UV absorbing layer 21 and the second UV absorbing layer 22 (described later), it is not easy to bleed out, and the light absorption function can be stably exerted.

[0107] R in the above formula (i-2) 4-1 and n have the same meanings as described in the above formula (i-1).

[0108] Compound (i) has excellent solubility in various solvents and / or affinity with various compounds. As the solvent, for example, alcohol solvents such as methanol, ethanol, ethylene glycol, isopropanol, 1-butanol, 2-butanol, propylene glycol, methyl cellosolve, butyl cellosolve, propylene glycol monomethyl ether, etc.; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol monomethyl ether acetate, ethyl lactate, etc.; ketone solvents such as acetone, 2-butanone, cyclopentanone, cyclohexanone, methyl amyl ketone, methyl isobutyl ketone, etc.; aliphatic hydrocarbon solvents such as pentane, hexane, heptane, etc.; aromatic hydrocarbon solvents such as toluene, xylene, mesitylene, etc.; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran, dimethoxyethane, 1,4-dioxane, etc.; and chlorinated hydrocarbon solvents such as dichloromethane, chloroform, chlorobenzene, etc.

[0109] In the solvent, there are hydrophilic solvents and hydrophobic solvents. For example, in the case of alcohol solvents, although it also depends on the number of carbon atoms, it is generally a hydrophilic solvent. On the other hand, aliphatic hydrocarbon solvents such as pentane, hexane, and heptane are generally hydrophobic solvents. From the viewpoint of not being easy to ooze out when containing compound (i) in polymer films such as adhesive sheets and optical films and the viewpoint of being able to expand the selectivity of the solvent, compound (i) is preferably soluble in a hydrophilic solvent or a hydrophobic solvent, more preferably soluble in a hydrophilic solvent and a hydrophobic solvent, i.e., amphiphilic.

[0110] The compound (i) preferably satisfies the relationship of the following formula (a).

[0111] ε(420) / ε(400)≤0.4 (a)

[0112] [In formula (a),

[0113] ε(420) represents the gram absorption coefficient at a wavelength of 420 nm.

[0114] ε(400) represents the gram absorption coefficient at a wavelength of 400 nm.

[0115] The unit of gram absorption coefficient is defined as L / (g·cm).]

[0116] In formula (a), the value of ε(420) / ε(400) represents the intensity of absorption at a wavelength of 400 nm relative to the intensity of absorption at a wavelength of 420 nm. The smaller the value, the more specific absorption is in the wavelength region near 400 nm compared to the absorption in the wavelength region near 420 nm. The smaller the value, the less yellowish the compound is and the more transparent it is. ε(420) / ε(400) can be calculated from ε(420) and ε(400) measured for the compound in an appropriate solvent using a spectrophotometer (e.g., UV3150 (manufactured by Shimadzu Corporation)).

[0117] When compound (i) satisfies the above formula (a), it absorbs light of wavelength 400nm, on the other hand, it is not easy to absorb light of wavelength 420nm, and it is not easy to absorb blue visible light. Therefore, compound (i) can be provided as a light absorber having a blue light cutoff function and not easy to hinder good color presentation, and can be used as an ultraviolet absorber. In addition, when the laminate contains the compound (i), the performance of the components constituting the laminate (for example, the first light absorption anisotropic layer and the second light absorption anisotropic layer, organic EL elements, liquid crystal display elements and other display elements) can be suppressed from being degraded by short-wavelength visible light (i.e., light near a wavelength of 400nm). The value of ε (420) / ε (400) of compound (i) is preferably 0.4 or less, more preferably 0.25 or less, further preferably 0.2 or less, particularly preferably 0.15 or less, particularly preferably 0.1 or less, very preferably 0.05 or less, for example 0.03 or less. The lower limit is not particularly limited, but is usually preferably 0.005 or more from the viewpoint of maintaining the absorption ability at around 400 nm by the compound (i).

[0118] The compound (i) preferably satisfies the relationships of the following formulae (b) and (c) in addition to the relationship of the above formula (a).

[0119] λmax<420 (b)

[0120] ε(400)≥40 (c)

[0121] [In formula (b), λmax represents the maximum absorption wavelength [nm] of compound (i).

[0122] In formula (c), ε(400) has the same meaning as described in formula (a).

[0123] When the above formulas (b) and (c) are satisfied, the maximum absorption of compound (i) exists on the wavelength side shorter than 420 nm, and it can be said that compound (i) is a compound that shows high absorption near a wavelength of 400 nm. By making compound (i) satisfy such a formula, the resin film, coating or laminating layer containing the compound (i) is not likely to affect the display characteristics and can have high light resistance. The maximum absorption wavelength λmax of compound (i) is more preferably less than 415 nm.

[0124] The content of the ultraviolet absorber is preferably 0.1 parts by mass to 30 parts by mass, and more preferably 0.5 parts by mass to 10 parts by mass, based on 100 parts by mass of the resin constituting the first UV absorbing layer 21 .

[0125] The first UV absorbing layer 21 may be a first base layer (described later) to which the first composition for forming the first light-absorbing anisotropic layer 11 is applied.

[0126] The first UV absorbing layer 21 is not particularly limited as long as it satisfies the relationship of the above formula (1), and may include, for example, one or more of a glass substrate containing an ultraviolet absorber, a resin film containing an ultraviolet absorber, and a coating layer containing an ultraviolet absorber. The first UV absorbing layer 21 preferably includes at least one of a resin film and a coating layer.

[0127] As the resin film and coating constituting the first UV absorbing layer 21, the following resin films and coatings can be cited. When the first UV absorbing layer 21 includes a resin film and a coating, it is preferred that at least one of the resin film and the coating contains an ultraviolet absorber. The ultraviolet absorber may also be a compound obtained by bonding a compound having ultraviolet absorption ability to a compound (monomer or polymer) of the resin constituting the resin film and the coating.

[0128] As the resin constituting the resin film, for example, olefin resins such as polyethylene and polypropylene; cyclic olefin resins having a ring system or norbornene structure; polyvinyl alcohol; polyethylene terephthalate; poly(meth)acrylate; cellulose ester resins such as cellulose triacetate, cellulose diacetate and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyethersulfone; polyetherketone; polyphenylene sulfide; polyphenylene ether, etc. Among them, from the viewpoint of transparency when used for optical film applications, a resin film selected from any one of cellulose triacetate, cyclic olefin resins, polymethacrylate, and polyethylene terephthalate is more preferred. The so-called "(meth)acrylic-" refers to at least one of "acrylic-" and "methacrylic-". The same applies to the expression of (meth)acryloyl, etc.

[0129] As the resin film, a commercially available cellulose ester resin film can be used. Examples of such cellulose ester resin films include "Fujitac Film" (manufactured by Fuji Photo Film Co., Ltd.); "KC8UX2M", "KC8UY" and "KC4UY" (all manufactured by Konica Minolta Opto Co., Ltd.).

[0130] As the cyclic olefin resin constituting the resin film, commercially available cyclic olefin resins can be used. As such cyclic olefin resins, "Topas" (registered trademark) (manufactured by Ticona (Germany)), "ARTON" (registered trademark) (manufactured by JSR Corporation), "ZEONOR" (registered trademark), "ZEONEX" (registered trademark) (manufactured by Zeon Corporation of Japan) and "Apel" (registered trademark) (manufactured by Mitsui Chemicals, Inc.) can be cited. These cyclic olefin resins can be made into resin films by film-forming using known means such as solvent casting and melt extrusion.

[0131] As the resin film, a commercially available cyclic olefin resin film may also be used. Examples of such cyclic olefin resin films include "Escena" (registered trademark), "SCA40" (registered trademark) (all manufactured by Sekisui Chemical Co., Ltd.), "ZEONORFILM" (registered trademark) (manufactured by OPTES Co., Ltd.), and "ARTONFILM" (registered trademark) (manufactured by JSR Co., Ltd.).

[0132] The thickness of the resin film is preferably 20 μm to 150 μm, 30 μm to 130 μm, 30 μm to 120 μm, 40 μm to 100 μm, or 40 μm to 80 μm.

[0133] Examples of the coating layer include: a layer formed by coating a hard coating layer forming composition, an easy-adhesion composition, a coupling agent, etc. on the surface of a substrate film; a layer formed by coating a reactive monomer or a reactive polymer, etc., and then irradiating the reactive monomer or the reactive polymer with active energy rays to graft polymerize the reactive monomer or the reactive polymer, etc. The coating layer is preferably a hard coating layer formed by coating a hard coating layer forming composition.

[0134] The hard coat layer is preferably a cured layer of a curable composition containing an active energy ray-curable resin, and more preferably a cured layer of a composition containing an ultraviolet-curable resin. The curable composition containing an ultraviolet-curable resin preferably contains a (meth)acrylic compound as a curable component. The (meth)acrylic compound is a compound having at least one (meth)acryloyl group, and may be a monomer, an oligomer, or a polymer.

[0135] As (meth) acrylic compounds, for example, (meth) acrylic compounds such as monofunctional (meth) acrylic ester compounds and multifunctional (meth) acrylic ester compounds; carbamate (meth) acrylic ester compounds such as multifunctional carbamate (meth) acrylic ester compounds; epoxy (meth) acrylic ester compounds such as multifunctional epoxy (meth) acrylic ester compounds; carboxyl modified epoxy (meth) acrylic ester compounds; polyester (meth) acrylic ester compounds, etc. can be mentioned. One or more of them can be used. Among them, multifunctional (meth) acrylic ester compounds or carbamate (meth) acrylic ester compounds are preferred, and it is more preferred to combine multifunctional (meth) acrylic ester compounds with carbamate (meth) acrylic esters.

[0136] The content of the multifunctional (meth)acrylate compound is preferably 50 to 100 parts by mass, more preferably 60 to 95 parts by mass, and further preferably 70 to 90 parts by mass, relative to 100 parts by mass of the solid content of the curable composition. In this specification, the solid content of the curable composition refers to the total amount of the components obtained by removing the solvent from the curable composition when the curable composition contains a solvent.

[0137] When the hard coat layer has ultraviolet absorbing ability, the hard coat layer can be formed using a compound obtained by bonding a compound having ultraviolet absorbing ability to the above-mentioned (meth)acrylic compound.

[0138] The curable composition may contain a polymerization initiator in addition to the curable component. Examples of the polymerization initiator include photopolymerization initiators and radical polymerization initiators, and known polymerization initiators may be used.

[0139] The curable composition can be cured by polymerizing a curable component such as a (meth)acrylic compound, after being applied onto a substrate film and then irradiated with active energy rays.

[0140] The hard coating layer preferably shows a value of 8B or harder in the pencil hardness test (measured by placing the first substrate layer on a glass plate) specified in JIS K 5600-5-4:1999 "General Test Methods for Coatings - Part 5: Mechanical Properties of Coatings - Section 4: Scratch Hardness (Pencil Method)", and may also be 5B or harder.

[0141] The thickness of the coating layer is preferably 0.1 μm to 20 μm, and may be 0.3 μm to 15 μm, 0.5 μm to 10 μm, or 1 μm to 8 μm.

[0142] As the base film for forming the coating, the above-mentioned resin film can be cited. For the base film, it can be incorporated together with the coating when the coating is incorporated into the laminate 1, 2, or it can be peeled off and removed. In the case of peeling the base film from the coating, it is preferred to apply a release agent or the like on the surface of the side of the base film to be formed with the coating so as to perform a demolding treatment. Thus, the base film can be peeled off and removed when the coating is incorporated into the laminate 1, 2.

[0143] The thickness of the first UV absorbing layer 21 is preferably 20 μm to 150 μm, or 30 μm to 130 μm, or 30 μm to 120 μm, or 40 μm to 100 μm, or 40 μm to 80 μm. By setting the thickness within the above range, when the first UV absorbing layer 21 is used as the first substrate layer for forming the first light-absorbing anisotropic layer 11, it can be thin enough to be practically handled, and have excellent strength and processability.

[0144] (Second UV Absorption Layer (Second Ultraviolet Absorption Layer))

[0145] The second UV absorbing layer 22 is a layer satisfying the relationship of the above formula (1). The T(380) of the second UV absorbing layer 22 is 20% or less, or 15% or less, or 10% or less, or 8% or less, or 5% or less, and is usually 0.01% or more. The T(380) of the second UV absorbing layer 22 may be the same as or different from the T(380) of the first UV absorbing layer 21, or may be smaller than the T(380) of the first UV absorbing layer 21.

[0146] The second UV absorbing layer 22 preferably also satisfies the relationship of the above formula (3). When the first UV absorbing layer 21 does not satisfy the relationship of the above formula (3), it preferably satisfies the relationship of the above formula (3). T(410) of the second UV absorbing layer 22 may be 90% or less, 50% or less, 20% or less, 18% or less, or 15% or less, and is usually 0.01% or more. T(410) of the second UV absorbing layer 22 may be the same as or different from T(410) of the first UV absorbing layer 21, or may be greater than or less than T(410) of the first UV absorbing layer 21. T(380) and T(410) of the second UV absorbing layer 22 may be measured as transmittances at wavelengths of 380 nm and 410 nm, respectively, using a spectrophotometer.

[0147] The second UV absorbing layer 22 preferably also satisfies the relationship of T(410) / T(450)≤0.9, more preferably satisfies the relationship of T(410) / T(450)≤0.5, and further preferably satisfies the relationship of T(410) / T(450)≤0.2. In the case where the first UV absorbing layer 21 does not satisfy this relationship, it is preferably satisfied in the second UV absorbing layer 22. By satisfying this relationship, light with a wavelength of less than 410 nm is absorbed, and on the other hand, light in the visible light region is not easily absorbed. Therefore, when assembled in a display device, a laminate can be provided that suppresses degradation caused by ultraviolet light and does not easily hinder good color presentation. It should be noted that the meanings of T(410) and T(450) are as described above.

[0148] The second UV absorbing layer 22 may be a single-layer structure or a multi-layer structure. When the second UV absorbing layer 22 is a single-layer structure, the second UV absorbing layer 22 is preferably a layer containing an ultraviolet absorber. When the second UV absorbing layer 22 has a multi-layer structure, more than one layer may have ultraviolet absorption capability, and preferably includes more than one layer containing an ultraviolet absorber. As the ultraviolet absorber contained in the second UV absorbing layer, a known ultraviolet absorber can be used. The ultraviolet absorbers described above as known ultraviolet absorbers can be cited, for example, the above-mentioned compound (i) can be used.

[0149] When the second light-absorbing anisotropic layer 12 is a liquid crystal film (described later), the second UV absorbing layer 22 may be a second substrate layer (described later) to which a second composition (described later) for forming the second light-absorbing anisotropic layer 12 is applied. Alternatively, the second UV absorbing layer 22 may be a first substrate layer (described later) to which a first composition (described later) for forming the first light-absorbing anisotropic layer 11 is applied.

[0150] The second UV absorbing layer 22 is not particularly limited as long as it satisfies the relationship of the above formula (1), and may include, for example, one or more of a glass substrate containing an ultraviolet absorber, a resin film containing an ultraviolet absorber, a coating layer containing an ultraviolet absorber, and a laminating layer. The second UV absorbing layer 22 preferably includes at least one of a resin film and a coating layer.

[0151] As the resin film and coating constituting the second UV absorbing layer 22, the resin film and coating described as the resin film and coating constituting the first UV absorbing layer 21 can be cited. When the second UV absorbing layer 22 includes a resin film and a coating, it is preferred that at least one of the resin film and the coating contains an ultraviolet absorber. The base film to be coated may be incorporated into the laminated bodies 1 and 2 as described in the first UV absorbing layer 21, or may be peeled off and removed.

[0152] It is preferred that the first UV absorbing layer 21 or the second UV absorbing layer 22 each independently satisfy the relationship of the following formula (9).

[0153] 80nm≤ReB(550)≤160nm (9)

[0154] [In formula (9), ReB(550) represents the in-plane phase difference value of the first UV absorbing layer 21 or the second UV absorbing layer 22 at a wavelength of 550 nm.]

[0155] ReB(550) may be 90 nm to 150 nm, 100 nm to 140 nm, or 110 nm to 130 nm. Preferably, the second UV absorbing layer 22 satisfies the relationship of the above formula (9), which can suppress the viewing angle dependence when the laminate 1 and 2 are applied to a display device. The ReB(550) of the first UV absorbing layer 21 or the second UV absorbing layer 22 can be measured using a phase difference measuring device.

[0156] The first UV absorbing layer 21 or the second UV absorbing layer 22 satisfying the relationship of the above formula (9) can be obtained by imparting a phase difference to a resin film or a coating contained in the first UV absorbing layer 21 or the second UV absorbing layer 22. For example, a stretched film can be cited as a resin film having a phase difference. A stretched film can be cited as a stretched film obtained by stretching the above resin film. A liquid crystal film can be cited as a coating having a phase difference.

[0157] The range of the angle θi formed by the slow axis of the first UV absorbing layer 21 or the second UV absorbing layer 22 and the absorption axis of the second light absorption anisotropic layer preferably satisfies the relationship of the following formula (10).

[0158] 15°≤|θi|≤75° (10)

[0159] When the first UV absorbing layer 21 or the second UV absorbing layer 22 satisfies the relationship of the above formula (10), it becomes a so-called 1 / 4 wavelength plate (λ / 4 plate) capable of converting linear polarized light into circular polarized light. In this case, the visual recognition when viewed from the front through polarized sunglasses is also excellent. In addition, when the second UV absorbing layer 22 satisfies the relationship of the above formula (10), the transmittance in the front direction of the laminate of this embodiment is excellent, and the directional anisotropy of the light absorption characteristics in the oblique direction is reduced, and the effect of reducing the hue difference between the front and the front is easily further improved even when viewed from the oblique direction. |θi| is more preferably in the range of 25°≤|θi|≤65°, and more preferably in the range of 35°≤|θi|≤55°. The angle θi formed by the slow axis of the first UV absorption layer 21 or the second UV absorption layer 22 and the absorption axis of the second light absorption anisotropic layer can be adjusted to the above range by, for example, the following methods: adjusting the bonding angle; making the slow axis of the first UV absorption layer 21 or the second UV absorption layer 22, or the absorption axis of the second light absorption anisotropic layer consistent with a specified angle in advance, and bonding in a roll-to-roll manner; etc.

[0160] (First light absorption anisotropic layer)

[0161] The first light absorption anisotropic layer 11 is formed of a first composition including one or more dichroic pigments and a liquid crystal compound, and satisfies the relationship of the above formula (2). Therefore, it is considered that the absorption axis of the dichroic pigment is oriented in the vertical direction relative to the plane of the first light absorption anisotropic layer 11, so that the first light absorption anisotropic layer 11 can effectively transmit light from the front direction and effectively absorb light from the oblique direction.

[0162] The first light absorption anisotropic layer 11 may contain two or more dichroic dyes. It is preferred that at least one of the dichroic dyes contained in the first light absorption anisotropic layer 11 is an azo compound.

[0163] The first light absorption anisotropic layer 11 is preferably a liquid crystal film. In this specification, the so-called liquid crystal film refers to a film obtained from a composition containing a liquid crystal compound. The liquid crystal film may contain a liquid crystal compound or a polymer of a liquid crystal compound. The polymer of a liquid crystal compound may or may not exhibit liquid crystal properties. The liquid crystal film constituting the first light absorption anisotropic layer 11 contains a dichroic pigment.

[0164] The liquid crystalline compound contained in the first composition is not particularly limited as long as it is a compound having liquid crystallinity, and may be a low-molecular liquid crystalline compound or a high-molecular liquid crystalline compound. The liquid crystalline compound may also be a polymerizable liquid crystalline compound having a polymerizable group. In the case where the liquid crystal film contains a polymer of a liquid crystalline compound, the liquid crystalline compound is usually a polymerizable liquid crystalline compound. The liquid crystalline compound is preferably a liquid crystalline compound capable of forming a smectic liquid crystal phase, and the liquid crystal film preferably contains a liquid crystalline compound capable of forming a smectic liquid crystal phase or a polymer of a liquid crystalline compound capable of forming a smectic liquid crystal phase. The dichroic dye and the liquid crystalline compound will be described later.

[0165] The absorbance Az in the z direction in the above formula (2) is measured by making light incident on the side surface of the first light absorption anisotropic layer 11, so it is difficult to measure. Therefore, when the angle formed by the vibration plane of the linearly polarized light as the measurement light and the x-y plane of the first light absorption anisotropic layer 11 is 90°, with respect to this vibration plane, the x-y plane of the first light absorption anisotropic layer 11 is inclined by 30° and 60° along the incident direction of the linearly polarized light for measurement, whereby the absorbance Az in the z direction can be calculated.

[0166] Specifically, it can be calculated by the following methods or the like.

[0167] In a state where the first light absorption anisotropic layer 11 is rotated by 30° and 60° about the y-axis, the same linearly polarized light as the linearly polarized light for which Ax was measured is made incident, whereby the absorbances Ax(z = 30°) and Ax(z = 60°) are measured respectively. Similarly, in a state where the first light absorption anisotropic layer 11 is rotated by 30° and 60° about the x-axis, the same linearly polarized light as the linearly polarized light for which Ay was measured is made incident, whereby the absorbances Ay(z = 30°) and Ay(z = 60°) are measured respectively.

[0168] At this time, if Ax(z = 30°) < Ax(z = 60°) and Ay(z = 30°) = Ay(z = 60°), then Ax(z = 30°) < Ax(z = 60°) < Ax(z = 90°) = Az, and if Ay(z = 30°) < Ay(z = 60°) and Ax(z = 30°) = Ax(z = 60°), then Ay(z = 30°) < Ay(z = 60°) < Ay(z = 90°) = Az. Therefore, it can be said that the relationship of formula (2) is necessarily satisfied.

[0169] Here, Ax(z = 90°) is the absorbance measured by making linearly polarized light identical to the linearly polarized light for which Ax was measured incident while the first light absorption anisotropic layer 11 is rotated 90° about the y-axis. Ay(z = 90°) is the absorbance measured by making linearly polarized light identical to the linearly polarized light for which Ax was measured incident while the first light absorption anisotropic layer 11 is rotated 90° about the x-axis.

[0170] Particularly, in the case where there is no absorption anisotropy in the x-y plane of the first light absorption anisotropic layer 11, that is, when Ax and Ay are equal, Ax(z = 30°) = Ay(z = 30°) and Ax(z = 60°) = Ay(z = 60°). Here, let Ax(z = 30°) = Ay(z = 30°) = A(z = 30°), let Ax(z = 60°) = Ay(z = 60°) = A(z = 60°), and let Ax(z = 90°) = Ay(z = 90°) = A(z = 90°). Thus, if A(z = 30°) < A(z = 60°), then the relationship A(z = 30°) < A(z = 60°) < A(z = 90°) = Az is satisfied. In addition, if A(z = 30°) > (Ax + Ay) / 2, it can be said that Az necessarily satisfies formula (2).

[0171] The above-mentioned Ax and Ay refer to the absorbances in the front direction of the first light absorption anisotropic layer 11. The smaller the values of Ax and Ay, the more precisely it can be said that the dichroic pigment in the first light absorption anisotropic layer 11 is oriented along the direction perpendicular to the plane. The values of Ax and Ay are preferably 0.3 or less. When greater than 0.3, the coloring in the front direction of the first light absorption anisotropic layer 11 becomes stronger, and thus there is a tendency for the front transmittance color difference when applied to a display device. Therefore, the values of Ax and Ay are each independently preferably 0.1 or less, more preferably 0.05 or less, and further preferably 0.02 or less. Additionally, the lower limit values of the values of Ax and Ay are each independently usually 0.001 or more, may be 0.003 or more, and may be 0.005 or more.

[0172] The above-mentioned Ax(z = 60°) and Ay(z = 60°) refer to the absorbances in the diagonal direction of the first light absorption anisotropic layer 11 and can be appropriately selected according to the light leaking diagonally in the display device. Ax(z = 60°) and Ay(z = 60°) are each independently preferably 1.0 or less, more preferably 0.5 or less, and further preferably 0.3 or less. Additionally, the lower limit value is usually 0.001 or more, may be 0.003 or more, and is 0.01 or more according to the necessity.

[0173] The first light absorption anisotropic layer 11 preferably satisfies the relationships of the following formulas (7) and (8).

[0174] Ax(z=60°) / Ax≥5 (7)

[0175] Ay(z=60°) / Ay≥5 (8)

[0176] [In formula (7), Ax(z=60°) is the absorbance of the maximum absorption wavelength of the first light absorption anisotropic layer 11 in the wavelength range of not less than 410 nm and not more than 780 nm, and represents the absorbance of linearly polarized light vibrating along the x-axis direction when the first light absorption anisotropic layer 11 is rotated 60° with the y-axis as the rotation axis.

[0177] In formula (8), Ay(z=60°) is the absorbance of the first light absorption anisotropic layer 11 at the maximum absorption wavelength, and represents the absorbance of linearly polarized light vibrating along the y-axis direction when the first light absorption anisotropic layer 11 is rotated 60° with the x-axis as the rotation axis.]

[0178] As for Ax(z=60°) / Ax in the above formula (7) and Ay(z=60°) / Ay in the formula (8), the larger the numerical value, the better the light absorption anisotropy is. For example, they are each independently preferably greater than 7, more preferably greater than 10, and further preferably less than 50.

[0179] The thickness of the first light absorption anisotropic layer 11 is preferably 0.1 μm to 10 μm, more preferably 0.5 μm to 5 μm, and even more preferably 0.5 μm to 2.5 μm. If the thickness of the first light absorption anisotropic layer 11 is less than 0.1 μm, the absorption of light from an oblique direction tends to be weak, and if the thickness is increased, the orientation of the dichroic dye tends to be disordered, so that the transmission characteristics in the front direction tend to be reduced.

[0180] (Dichroic Pigments)

[0181] The first light absorption anisotropic layer includes one or more dichroic pigments. The so-called dichroic pigment refers to a pigment having a property that the absorbance in the long axis direction of the molecule is different from the absorbance in the short axis direction of the molecule. As a dichroic pigment, it is preferred to have a characteristic of absorbing visible light, and more preferably has a maximum absorption wavelength (λmax) within the range of 380 to 680 nm.

[0182] As such dichroic pigment, for example, acridine pigment, oxazine pigment, cyanine pigment, naphthalene pigment, azo pigment and anthraquinone pigment etc. can be enumerated, wherein, preferably azo pigment.As azo pigment, monoazo pigment, disazo pigment, triazo pigment, tetraazo pigment and stilbene azo pigment etc. can be enumerated, preferably disazo pigment and triazo pigment.Dichroic pigment can be separately also can combine more than 2 kinds, but preferably according to the wavelength range of light absorption anisotropy requirement in the 1st light absorption anisotropic layer and use in combination more than 2 kinds.

[0183] Examples of the azo dye include compounds represented by formula (I).

[0184] T 1 -A 1 (-N=NA 2 ) p -N=NA 3 -T 2 (I)

[0185] [In formula (I),

[0186] A 1 , A 2 and A 3 each independently represents a 1,4-phenylene group which may have a substituent, a naphthalene-1,4-diyl group which may have a substituent, a benzoic acid phenyl ester group which may have a substituent, a 4,4′-stilbene group which may have a substituent, or a divalent heterocyclic group which may have a substituent,

[0187] T 1 and T 2 It represents an electron-withdrawing group or an electron-releasing group, and is located at a position substantially 180° with respect to the azo bond plane.

[0188] p represents an integer of 0 to 4. When p is 2 or more, each A 2 They can be the same or different from each other.

[0189] In the range that shows absorption in the visible light region, the -N=N- bond can be replaced by a -C=C-, -COO-, -NHCO-, or -N=CH- bond.]

[0190] The content of the dichroic pigment in the first light absorption anisotropic layer is preferably 0.1 to 30 parts by mass, or 0.5 to 20 parts by mass, or 1 to 10 parts by mass, or 1 to 5 parts by mass, relative to 100 parts by mass of the first light absorption anisotropic layer. The content ratio of the dichroic pigment in the first light absorption anisotropic layer can be calculated as the ratio of the dichroic pigment relative to 100 parts by mass of the solid content of the first composition used to form the first light absorption anisotropic layer. The so-called solid content of the first composition refers to all components after removing volatile components such as organic solvents from the first composition.

[0191] The content of the dichroic pigment contained in the first composition (the total amount when multiple types are included) is generally 1 to 60 parts by mass, preferably 1 to 40 parts by mass, and more preferably 1 to 20 parts by mass relative to 100 parts by mass of the liquid crystal compound from the viewpoint of obtaining good light absorption characteristics. When the content of the dichroic pigment is less than this range, light absorption becomes insufficient and sufficient light absorption anisotropy characteristics cannot be obtained. When the content of the dichroic pigment is more than this range, there is a situation where the orientation of the liquid crystal molecules of the liquid crystal compound is hindered.

[0192] (Liquid crystal compound and polymer thereof)

[0193] The liquid crystal compound contained in the first composition for forming the first light absorption anisotropic layer is used to orient the dichroic pigment through the guest-host interaction. The liquid crystal compound can be a low molecular liquid crystal compound or a high molecular liquid crystal compound. The liquid crystal compound can also be a polymerizable liquid crystal compound. The liquid crystal compound is preferably a compound that can form a smectic liquid crystal layer.

[0194] The polymerizable liquid crystal compound is a compound having a polymerizable group and having liquid crystal properties. The polymerizable group refers to a group participating in the polymerization reaction, preferably a photopolymerizable group. Here, the so-called photopolymerizable group refers to a group that can participate in the polymerization reaction using active free radicals, acids, etc. generated by the photopolymerization initiator described later. As the polymerizable group, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxacyclopropyl, oxetane, etc. can be cited. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxacyclopropyl and oxetane are preferred, and methacryloyloxy or acryloyloxy are more preferred. The liquid crystal can be a thermotropic liquid crystal or a lyotropic liquid crystal. When mixed with the above-mentioned dichroic pigment, it is preferably a thermotropic liquid crystal.

[0195] When the polymerizable liquid crystal compound is a thermotropic liquid crystal, it can be a thermotropic liquid crystal compound showing a nematic liquid crystal phase, or it can be a thermotropic liquid crystal compound showing a smectic liquid crystal phase. When the light absorption anisotropy is presented in the form of a liquid crystal cured film (liquid crystal film) by polymerization reaction, the liquid crystal state displayed by the polymerizable liquid crystal compound is preferably a smectic phase, and when it is a high-order smectic phase, it is more preferred from the viewpoint of high performance. Among them, it is more preferred to form a high-order smectic liquid crystal compound of smectic B phase, smectic D phase, smectic E phase, smectic F phase, smectic G phase, smectic H phase, smectic I phase, smectic J phase, smectic K phase or smectic L phase, and it is further preferred to form a high-order smectic liquid crystal compound of smectic B phase, smectic F phase or smectic I phase. If the liquid crystal phase formed by the polymerizable liquid crystal compound is these high-order smectic phases, it is possible to manufacture the first light absorption anisotropic layer with higher light absorption anisotropy. The first light absorption anisotropic layer having high light absorption anisotropy can obtain a Bragg peak derived from a high-order structure such as a hexagonal phase or a crystalline phase in X-ray diffraction measurement. The Bragg peak is a peak derived from a periodic structure of molecular orientation. For the first light absorption anisotropic layer, the periodic interval can be From the viewpoint of obtaining higher light absorption anisotropic characteristics, it is preferred that the first light absorption anisotropic layer contains a polymer of a polymerizable liquid crystal compound aligned in a smectic phase.

[0196] The polymerizable liquid crystal compound may be a monomer, an oligomer obtained by polymerizing a polymerizable group, or a polymer. As such a polymerizable liquid crystal compound, a known polymerizable liquid crystal compound may be used, for example, a polymerizable liquid crystal compound described in Japanese Patent Publication No. 2020-76920 and Japanese Patent No. 6728581 may be cited.

[0197] When the liquid crystal compound is the above-mentioned polymer liquid crystal compound, a known liquid crystal compound can be used as the liquid crystal compound, and examples thereof include liquid crystal compounds described in JP-A-2011-237513 and the like.

[0198] One liquid crystal compound may be used alone or in combination of two or more. The content of the liquid crystal compound in the first light absorption anisotropic layer is preferably 40 to 99.9 parts by mass, or 60 to 99 parts by mass, or 70 to 99 parts by mass. If the content of the liquid crystal compound or polymer is within the above range, the orientation of the liquid crystal compound when the first light absorption anisotropic layer is formed tends to be higher. The proportion of the liquid crystal compound or its polymer in the first light absorption anisotropic layer can be calculated as the proportion of the liquid crystal compound in the first composition relative to 100 parts by mass of the solid content of the first composition (described later) used to form the light absorption anisotropic layer.

[0199] (Method for producing the first light absorption anisotropic layer)

[0200] The first light absorption anisotropic layer can be formed, for example, by coating a first composition containing at least one dichroic dye and a liquid crystal compound on a first substrate layer. The first substrate layer can be the resin film described above for the first UV absorption layer, or a substrate film having a coating layer formed thereon.

[0201] The coating layer formed by coating the first composition may be subjected to a drying treatment for removing the solvent or the like to form a first light absorption anisotropic layer. When the first composition contains a polymerizable liquid crystal compound as a liquid crystal compound, the coating layer after the drying treatment may be irradiated with active energy rays or the like to polymerize the polymerizable liquid crystal compound, thereby forming a first light absorption anisotropic layer as a cured layer of the polymerizable liquid crystal compound. The first composition may be coated on the surface of the first substrate layer, or on the surface of the first orientation layer formed on the surface of the first substrate layer.

[0202] The content of the dichroic pigment in the first composition (the total amount when it contains multiple kinds) can be appropriately determined according to the type of dichroic pigment, but from the viewpoint of obtaining good light absorption characteristics, for example, relative to 100 parts by mass of the liquid crystal compound, it can be more than 1 part by mass and less than 60 parts by mass, it can also be more than 1 part by mass and less than 40 parts by mass, it can also be more than 1 part by mass and less than 20 parts by mass. When the content of the dichroic pigment is less than the above-mentioned range, there is a situation where the light absorption capacity of the first light absorption anisotropic layer becomes insufficient and sufficient light absorption anisotropy cannot be obtained. When the content of the dichroic pigment is more than the above-mentioned range, there is a situation where the orientation of the liquid crystal compound is hindered.

[0203] The first composition may further include a solvent in addition to the dichroic pigment and the liquid crystal compound. Usually, the viscosity of the liquid crystal compound is high, so in many cases, it is dissolved in a solvent to make the first composition including the solvent, whereby coating to the first substrate layer becomes easy, and as a result, the first light absorption anisotropic layer is easily formed. As the solvent, it is preferably a solvent that can completely dissolve the liquid crystal compound, and in addition, it is preferably an inactive solvent for the polymerization reaction of the liquid crystal compound. Examples of the solvent include alcohol solvents such as methanol, ethanol, ethylene glycol, isopropanol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorinated solvents such as chloroform and chlorobenzene; amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone, and 1,3-dimethyl-2-imidazolidinone, etc. These solvents may be used alone or in combination of two or more.

[0204] The content of the solvent in the first composition is preferably 50 to 98% by mass relative to the total amount of the first composition. In other words, the content of the solid component in the first composition is preferably 2 to 50% by mass, and more preferably 5 to 30% by mass. If the content of the solid component is 50% by mass or less, the viscosity of the first composition becomes low, so it is easy to form the first light absorption anisotropic layer with a substantially uniform thickness, and there is a tendency that unevenness is not easily generated in the first light absorption anisotropic layer. The content of the solid component can be determined in consideration of the thickness of the first light absorption anisotropic layer to be manufactured.

[0205] The first composition may further include a polymerization initiator such as a photopolymerization initiator or a thermal polymerization initiator, a non-liquid crystal compound having a polymerizable group, a leveling agent, an antioxidant, a photosensitizer, and other additives. When the first composition is directly coated on the surface of the first substrate layer (when the first orientation layer is not used), the first composition preferably further includes an orientation promoter.

[0206] The polymerization initiator can be used when the first composition contains a compound participating in the polymerization reaction, such as a polymerizable liquid crystal compound, and is a compound capable of initiating the polymerization reaction of the compound. As a polymerization initiator initiating the polymerization reaction of the polymerizable liquid crystal compound, a photopolymerization initiator that generates active free radicals by the action of light is preferred from the viewpoint of not depending on the phase state of the thermotropic liquid crystal.

[0207] The photopolymerization initiator may be any compound capable of initiating a polymerization reaction of a polymerizable liquid crystal compound or the like, and a known photopolymerization initiator may be used. Specifically, a photopolymerization initiator capable of generating active free radicals or acids by the action of light may be mentioned, and a photopolymerization initiator capable of generating free radicals by the action of light is preferred. The photopolymerization initiator may be used alone or in combination of two or more.

[0208] The photopolymerization initiator can use a known photopolymerization initiator. For example, as a photopolymerization initiator that generates active free radicals, the following can be used:

[0209] Self-cleavable benzoin compounds, acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, oxime ester compounds, acylphosphine oxide compounds, azo compounds, etc.; and

[0210] Hydrogen-abstracting benzophenone compounds, alkyl phenone compounds, benzoin ether compounds, benzyl ketal compounds, dibenzosuberone compounds, anthraquinone compounds, xanthone compounds, thioxanthone compounds, halogenated acetophenone compounds, dialkoxyacetophenone compounds, halogenated bisimidazole compounds, halogenated triazine compounds, triazine compounds, etc.

[0211] As the photopolymerization initiator that generates an acid, iodonium salts, sulfonium salts, and the like can be used.

[0212] The photopolymerization initiator is preferably a self-cleavage type photopolymerization initiator from the viewpoint of excellent reaction efficiency at low temperatures, and is particularly preferably an acetophenone compound, a hydroxyacetophenone compound, an α-aminoacetophenone compound, or an oxime ester compound.

[0213] The content of the polymerization initiator in the first composition can be appropriately adjusted according to the type and amount of the polymerizable liquid crystal compound, and is generally 0.1 to 30 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 0.5 to 8 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound. If the content of the polymerization initiator is within the above range, polymerization can be performed without disturbing the orientation of the polymerizable liquid crystal compound.

[0214] A non-liquid crystal compound having a polymerizable group (hereinafter, sometimes referred to as a "non-liquid crystal compound"). It is a compound having a polymerizable group but not having liquid crystal. As the polymerizable group possessed by the non-liquid crystal compound, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, (methyl) acryloyl, (methyl) acryloyloxy, oxirane, oxetane, etc. can be cited. Among them, preferred polymerizable groups are (methyl) acryloyl, (methyl) acryloyloxy, vinyloxy, oxirane and oxetane, more preferred polymerizable groups are (methyl) acryloyl and (methyl) acryloyloxy, and further preferred polymerizable groups are (methyl) acryloyloxy. The polymerizable group in the non-liquid crystal compound can be one kind or a combination of two or more kinds, but is preferably a polymerizable group identical to the polymerizable group possessed by the liquid crystal compound.

[0215] The number of polymerizable groups possessed by the non-liquid crystal compound is not particularly limited, and may be, for example, 1 to 20. However, from the viewpoint of further improving the film strength of the first light absorption anisotropic layer, the number is preferably 2 to 10, and more preferably 3 to 6. When the non-liquid crystal compound has two or more polymerizable groups, the polymerizable groups may be the same or different from each other.

[0216] As non-liquid crystal compounds having polymerizable groups, monofunctional (meth)acrylates and multifunctional (meth)acrylates can be cited. Monofunctional acrylates and multifunctional acrylates as non-liquid crystal compounds having polymerizable groups are non-liquid crystal and therefore preferably do not have a mesogenic structure. Monofunctional acrylates and multifunctional acrylates may contain a carbamate structure, an amino structure, an epoxy structure, an ethylene glycol structure and / or a polyester structure in the molecule.

[0217] The so-called leveling agent is an additive that has the function of adjusting the fluidity of the composition and making the film obtained by coating the composition flatter. As the leveling agent, for example, organic modified silicone oil-based, polyacrylate-based and perfluoroalkyl-based leveling agents can be cited. Among them, polyacrylate-based leveling agents and perfluoroalkyl-based leveling agents are preferred.

[0218] When the first composition contains a leveling agent, the content is preferably 0.01 to 5 parts by mass, and more preferably 0.05 to 3 parts by mass, relative to 100 parts by mass of the content of the liquid crystal compound. If the content of the leveling agent is within the above range, it is easy to orient the liquid crystal compound, and the obtained first light absorption anisotropic layer tends to become smoother. If the content of the leveling agent relative to the liquid crystal compound exceeds the above range, it is easy to produce unevenness in the obtained first light absorption anisotropic layer. It should be noted that the first composition may contain two or more leveling agents.

[0219] The first composition can be obtained by stirring a dichroic dye and a liquid crystal compound, and, if necessary, additives such as a solvent, a non-liquid crystal compound, an alignment promoter, a polymerization initiator, and a leveling agent.

[0220] Examples of a method for applying the first composition include known methods such as coating methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and applicator coating, and printing methods such as flexographic methods.

[0221] The coating layer of the first composition formed on the first substrate layer is preferably dried. When the first composition contains a solvent, the solvent in the coating layer can be removed by drying the coating layer. As the drying method, known methods can be mentioned, and one or more methods such as natural drying, heating drying, ventilation drying, and reduced pressure drying can be mentioned.

[0222] The drying conditions in the drying process can be appropriately determined according to the components contained in the first composition. For example, the drying temperature in the drying process is 50° C. to 150° C., or 60° C. to 120° C. The drying time in the drying process is 15 seconds to 10 minutes, or 0.5 minutes to 5 minutes.

[0223] When heat treatment is performed during the drying treatment, the liquid crystal compound contained in the first composition may be heated to a temperature higher than the liquid crystal phase transition temperature at which the liquid crystal compound undergoes phase transition, thereby orienting the liquid crystal compound while removing the solvent in the coating layer. Thus, the liquid crystal compound can be oriented in a vertical direction relative to the surface of the first light absorption anisotropic layer, and the dichroic pigment can also be oriented along with the orientation of the liquid crystal compound.

[0224] Alternatively, when a first orientation layer is provided on the surface of the first substrate layer, the liquid crystal compound and the dichroic dye in the coating layer can be oriented by utilizing the orientation control force of the first orientation layer.

[0225] When the first composition does not contain a polymerizable liquid crystal compound, the first light absorption anisotropic layer can be obtained by aligning the liquid crystal compound and the dichroic dye as described above and then removing the solvent.

[0226] When the first composition contains a polymerizable liquid crystal compound, the coating layer formed on the first substrate layer can be dried, and active energy rays can be irradiated while the polymerizable liquid crystal compound and the dichroic pigment are oriented to polymerize and cure the polymerizable liquid crystal compound, thereby forming a first light-absorbing anisotropic layer in which the liquid crystal compound and the dichroic pigment are oriented.

[0227] As a method for polymerizing a polymerizable liquid crystal compound, photopolymerization is preferred. Photopolymerization can be implemented by irradiating a laminated structure of a coating layer obtained by coating a first composition containing a polymerizable liquid crystal compound on a first substrate layer or a first orientation layer with active energy rays. As the active energy rays irradiated, it can be appropriately selected according to the type of polymerizable liquid crystal compound contained in the coating layer (especially the type of photopolymerizable functional group possessed by the polymerizable liquid crystal compound), the type of photopolymerization initiator when a photopolymerization initiator is included, and their amount. Specifically, one or more lights selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, α rays, β rays and γ rays can be cited. Among them, from the aspect of easily controlling the progress of the polymerization reaction and the aspect that a device widely used in the art can be used as a photopolymerization device, ultraviolet light is preferred, and the type of polymerizable liquid crystal compound is preferably selected in a manner that can be photopolymerized using ultraviolet light.

[0228] As the light source of active energy rays, for example, there can be mentioned a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a tungsten lamp, a gallium lamp, an excimer laser, an LED light source emitting light in a wavelength range of 380 to 440 nm, a chemical lamp, a black light lamp, a microwave-excited mercury lamp, a metal halide lamp, and the like.

[0229] The UV radiation intensity is usually 10mW / cm 2 ~3,000mW / cm 2 The ultraviolet irradiation intensity is preferably an intensity in a wavelength region effective for activating a cationic polymerization initiator or a free radical polymerization initiator. The irradiation time is usually 0.1 seconds to 10 minutes, preferably 1 second to 5 minutes, more preferably 5 seconds to 3 minutes, and further preferably 10 seconds to 1 minute. When irradiation is performed once or multiple times with such an ultraviolet irradiation intensity, the cumulative light amount is 10 mJ / cm 2 ~3,000mJ / cm 2 , preferably 50 mJ / cm 2 ~2,000mJ / cm 2 , more preferably 100 mJ / cm 2 ~1,000mJ / cm 2 When the accumulated light amount is below this range, the curing of the polymerizable liquid crystal compound may be insufficient, and good transferability may not be obtained when the first light absorbing anisotropic layer is transferred to an adherend. On the contrary, when the accumulated light amount is above this range, the first light absorbing anisotropic layer may be colored.

[0230] The first orientation layer facilitates the liquid crystal orientation of the liquid crystal compound. The state of the liquid crystal orientation varies depending on the properties of the first orientation layer and the liquid crystal compound, and their combination can be arbitrarily selected.

[0231] When the first orientation layer is formed of an orientation polymer, the orientation control force can be arbitrarily adjusted by the surface state and the friction conditions. When the first orientation layer is formed of a photo-orientation polymer, the orientation control force can be arbitrarily adjusted by the polarized light irradiation conditions, etc. In addition, the liquid crystal orientation can also be controlled by selecting the surface tension, liquid crystal properties, etc. of the liquid crystal compound.

[0232] As the first orientation layer formed between the first substrate layer and the first light absorbing anisotropic layer, it is preferred that the first orientation layer is insoluble in the solvent used when forming the first light absorbing anisotropic layer on the first orientation layer and has heat resistance in the heating treatment for removing the solvent and aligning the liquid crystal. As the first orientation layer, there can be cited a polymer orientation layer formed of an aligning polymer, a photo-alignment layer and a groove orientation layer, a stretched film stretched along the orientation direction, etc. In the case of being applied to a long roll film, the photo-alignment layer is preferred from the aspect of being able to easily control the orientation direction.

[0233] The thickness of the first orientation layer is usually in the range of 10 nm to 5000 nm, preferably in the range of 10 nm to 1000 nm, and more preferably in the range of 30 to 300 nm.

[0234] As the oriented polymer used in the rubbing orientation layer, polyamides, gelatins, polyimides with amide bonds in the molecule and polyamic acids, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinyl pyrrolidone, polyacrylic acid and polyacrylates, etc., which are hydrolyzates thereof, can be cited. Among them, polyvinyl alcohol is preferred. These oriented polymers can be used alone or in combination of two or more.

[0235] The rubbing method includes a method in which a film of an oriented polymer formed on the surface of the first substrate layer by applying the oriented polymer composition to the first substrate layer and annealing the oriented polymer composition is brought into contact with a rotating rubbing roller wound with a rubbing cloth.

[0236] The photo-alignment layer is formed of a polymer, oligomer or monomer having a photoreactive group. For the photo-alignment layer, the alignment control force can be obtained by irradiating the coating layer formed by coating the composition for forming the photo-alignment layer on the first substrate layer with polarized light. From the perspective that the direction of the alignment control force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light, the photo-alignment layer is more preferred.

[0237] The so-called photoreactive group refers to a group that generates liquid crystal orientation ability by irradiation with light. Specifically, it is a group that generates photoreactions such as orientation induction or isomerization reaction, dimerization reaction, photocrosslinking reaction or photodecomposition reaction of molecules generated by irradiation with light, which is the source of liquid crystal orientation ability. Among the photoreactive groups, groups that undergo dimerization reaction or photocrosslinking reaction are preferred from the perspective of excellent orientation. As a photoreactive group capable of the above reaction, it is preferably a group having an unsaturated bond, especially a double bond, and more preferably a group having at least one selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond) and a carbon-oxygen double bond (C=O bond).

[0238] As photoreactive groups with C=C bonds, for example, vinyl, polyene, stilbene, stilbazolyl, stilbazolinium, chalcone and cinnamoyl groups can be cited. From the perspective of easy control of reactivity and the presentation of orientation control force during photo-orientation, chalcone and cinnamoyl groups are preferred. As photoreactive groups with C=N bonds, groups with structures such as aromatic Schiff bases and aromatic hydrazones can be cited. As photoreactive groups with N=N bonds, groups with azobenzene as the basic structure, such as azobenzene, azonaphthyl, aromatic heterocyclic azo, disazo and formazan, can be cited. As photoreactive groups with C=O bonds, benzophenone, coumarin, anthraquinone and maleimide groups can be cited. These groups can have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid and halogenated alkyl.

[0239] In order to irradiate polarized light, it can be a method of directly irradiating polarized light from the film surface of the coating layer of the composition for forming the photo-alignment layer, or it can be a method of irradiating polarized light from the first substrate layer side and allowing the polarized light to pass through for irradiation. In addition, the polarized light is particularly preferably substantially parallel light. The wavelength of the irradiated polarized light is the wavelength of the wavelength region in which the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) in the range of 250 to 400nm is particularly preferred. As the light source used in the polarized light irradiation, xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, KrF, ArF and other ultraviolet lasers can be cited, and high-pressure mercury lamps, ultra-high-pressure mercury lamps and metal halide lamps are more preferred. The luminous intensity of ultraviolet light with a wavelength of 313nm of these lamps is large, so it is preferred. The light from the above-mentioned light source can be irradiated through an appropriate polarizer, thereby irradiating polarized light. As the polarizer, a polarizing filter, a polarizing prism such as Glan-Thompson or Glan-Taylor, or a wire grid type polarizer can be used.

[0240] (Second light absorption anisotropic layer)

[0241] The second light absorption anisotropic layer 12 has an absorption axis in a direction horizontal to its plane. The second light absorption anisotropic layer 12 is, for example, a polarizer obtained by uniaxially orienting a dichroic dye as a dye having light absorption anisotropy. Examples of polarizers obtained by uniaxially orienting a dichroic dye include: a polarizer formed by uniaxially stretching a polymer such as a polyvinyl alcohol resin impregnated with iodine or an organic dichroic dye; a polarizer formed by orienting a dichroic dye and a compound having liquid crystal properties using a composition including a polymerizable liquid crystal compound or the like and a dichroic dye. Such a polarizer utilizes a dichroic dye encapsulated in a stretched film or a liquid crystal compound to anisotropically absorb light, thereby being able to exhibit a polarization function of transmitting linearly polarized light having a vibration plane orthogonal to the absorption axis when non-polarized light is incident.

[0242] The second light absorption anisotropic layer can be a stretched polarizing film obtained by adsorbing a pigment having absorption anisotropy on a polymer such as a polyvinyl alcohol resin as described above (hereinafter, a stretched polarizing film obtained by using a polyvinyl alcohol resin as a polymer is sometimes referred to as a "PVA polarizing film"); a liquid crystal polarizing film comprising a polarizing layer of a liquid crystal film formed by applying a second composition containing a pigment having absorption anisotropy and a compound having liquid crystal properties to a substrate film. As a pigment having absorption anisotropy, a dichroic pigment can be cited. The dichroic pigment contained in the PVA polarizing film is preferably iodine.

[0243] The PVA polarizing film can be obtained through the following steps: a step of uniaxially stretching a polyvinyl alcohol resin film (hereinafter sometimes referred to as a "PVA film"); a step of dyeing the PVA film with a dichroic pigment to adsorb the dichroic pigment; a step of treating the PVA resin film adsorbed with the dichroic pigment with an aqueous boric acid solution; and a step of washing with water after the treatment with an aqueous boric acid solution as needed.

[0244] When the second light absorption anisotropic layer is a PVA polarizing film, the thickness of the second light absorption anisotropic layer is usually 30 μm or less, preferably 18 μm or less, more preferably 15 μm or less, and further preferably 10 μm or less. The thickness is usually 1 μm or more, for example, 5 μm or more.

[0245] The uniaxial stretching of the PVA film can be performed before, at the same time as, or after dyeing based on a dichroic pigment. In the case of uniaxial stretching after dyeing, the uniaxial stretching can be performed before or during the boric acid treatment. Of course, uniaxial stretching can also be performed in multiple stages as shown here. In uniaxial stretching, a method of uniaxial stretching along the film conveying direction between rollers with different circumferential speeds, a method of uniaxial stretching along the film conveying direction using a hot roller, a method of stretching along the width direction using a tenter, etc. can be adopted. Uniaxial stretching can be implemented by dry stretching in the atmosphere, or by wet stretching in a state where the PVA film is swollen using a solvent such as water. The stretching ratio is usually about 3 to 8 times. In addition, a drying treatment can be performed after applying an aqueous solution containing polyvinyl alcohol on the thermoplastic resin film, and the film can be stretched together with the thermoplastic resin film by the above method.

[0246] The dyeing of the PVA film with a dichroic dye can be performed, for example, by immersing the PVA film in an aqueous solution containing the dichroic dye. Specifically, iodine and a dichroic organic dye can be used as the dichroic dye.

[0247] A liquid crystal polarizing film formed by a second composition comprising a pigment having absorption anisotropy and a compound having liquid crystal properties can be suitably used, for example, in flexible displays, from the perspectives of being able to arbitrarily control the hue, being able to be significantly thinned, and being non-shrinkable due to the absence of stretching relaxation caused by heat.

[0248] The liquid crystal polarizing film can be obtained, for example, by coating the second composition on the second substrate layer, orienting the dichroic pigment contained in the second composition to form a second light absorption anisotropic layer. In the second light absorption anisotropic layer contained in the liquid crystal polarizing film, the dichroic pigment and the compound having liquid crystallinity or its polymer are horizontally oriented relative to the second substrate layer.

[0249] The thickness of the second light absorption anisotropic layer (liquid crystal film) included in the liquid crystal polarizing film is preferably 0.1 μm to 5 μm, more preferably 0.3 μm to 4 μm, and further preferably 0.5 μm to 3 μm. If the thickness is smaller than this range, sometimes the necessary light absorption cannot be obtained, and if the thickness is larger than this range, there is a tendency that the orientation control force brought by the second orientation layer (described later) is reduced and orientation defects are easily generated.

[0250] For the second light absorption anisotropic layer (liquid crystal film) included in the liquid crystal polarizing film, the ratio of the absorbance A1 (λ) in the orientation direction for light of wavelength λ [nm] to the absorbance A2 (λ) in the direction perpendicular to the plane relative to the orientation direction (dichroic ratio; A1 / A2) is preferably 7 or more, more preferably 20 or more, and further preferably 40 or more. The larger the value of the dichroic ratio, the more excellent the absorption selectivity of the second light absorption anisotropic layer. Although it also depends on the type of dichroic dye, when the liquid crystal film (liquid crystal cured film) included in the liquid crystal polarizing film is cured in the state of a nematic liquid crystal phase, the above-mentioned dichroic ratio is about 5 to 10.

[0251] By mixing two or more dichroic pigments with different absorption wavelengths, a second light absorption anisotropic layer of various hues can be produced, and a second light absorption anisotropic layer having absorption in the entire visible light range can be produced. By producing a second light absorption anisotropic layer with such absorption characteristics, it can be expanded to various uses.

[0252] As the second substrate layer, the substrate layer described in the first substrate layer can be cited. The second substrate layer can be peeled off and removed when incorporated into the laminate, or it can be used as a protective film for the second light absorption anisotropic layer without being peeled off and removed. As the dichroic pigment used in the liquid crystal polarizing film, the dichroic pigment used in the first light absorption anisotropic layer can be cited. As the compound having liquid crystal properties, rod-shaped liquid crystal compounds, disc-shaped liquid crystal compounds and mixtures thereof can be used. As the compound having liquid crystal properties, polymerizable liquid crystal compounds are preferably used. The liquid crystal compounds described in the first light absorption anisotropic layer can also be used for the compound having liquid crystal properties and the polymerizable liquid crystal compound.

[0253] The liquid crystal polarizing film may include a second orientation layer. The second orientation layer is preferably a horizontal orientation layer that can orient the liquid crystal compound in a horizontal direction relative to the surface of the liquid crystal polarizing film. The second orientation layer may include a polymer orientation layer formed by an orientation polymer, a light orientation layer formed by a light orientation polymer, and a groove orientation layer having a concave-convex pattern and a plurality of grooves (grooves) on the surface of the layer. From the viewpoint of the accuracy and quality of the orientation angle, the second orientation layer is preferably a light orientation layer. As the above-mentioned orientation layers constituting the second orientation layer, the orientation layer described in the first orientation layer may be mentioned.

[0254] (Polarizing plate)

[0255] Polarizing plate is a linear polarizing plate having a protective film on one or both sides of the second light absorbing anisotropic layer. The second light absorbing anisotropic layer can be incorporated into the laminate in the form of a polarizing plate. The protective film can use a thermoplastic resin film. The thermoplastic resin film can be surface treated (for example, corona treatment, etc.) to improve the adhesion with the second light absorbing anisotropic layer, or a thin layer such as a primer layer (also referred to as a primer layer) can be formed. The second light absorbing anisotropic layer and the protective film can be directly connected, or can be laminated via a laminating layer (adhesive layer or adhesive layer).

[0256] Thermoplastic resins constituting the thermoplastic resin film are preferably transparent films, and examples thereof include cellulose resins such as cellulose triacetate; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; polyethersulfone resins; polysulfone resins; polycarbonate resins; polyamide resins such as nylon and aromatic polyamide; polyimide resins; polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; cyclic polyolefin resins having a ring system and a norbornene structure (also referred to as norbornene resins); (meth)acrylic resins; polyarylate resins; polystyrene resins; polyvinyl alcohol resins, etc. Among them, the thermoplastic resin film is preferably a cyclic polyolefin resin film, a cellulose ester resin film, a polyester resin film, or a (meth)acrylic resin film.

[0257] The protective film can be obtained by forming a hard coating on a thermoplastic resin film. The hard coating can be formed on one side of the thermoplastic resin film or on both sides. By providing a hard coating, a thermoplastic resin film with improved hardness and scratch resistance can be made. The hard coating is, for example, a cured layer of an active energy ray-curable resin, preferably an ultraviolet-curable resin. As ultraviolet-curable resins, for example, (meth) acrylic resins, silicone resins, polyester resins, urethane resins, amide resins, epoxy resins, etc. can be cited. The hard coating can contain additives to increase strength. The additives are not particularly limited, and inorganic particles, organic particles, or mixtures thereof can be cited.

[0258] The thickness of the protective film is preferably 5 μm to 150 μm, and may be 10 μm to 100 μm, or 10 μm to 80 μm.

[0259] (Phase difference body)

[0260] The laminate 2 may include a phase difference body 13 including one or more phase difference layers on the side opposite to the second UV absorbing layer 22 side of the second light absorption anisotropic layer 12. The phase difference body 13 preferably includes one or more phase difference layers having an in-plane phase difference, and may further include a phase difference layer having a phase difference in the thickness direction.

[0261] When the second light absorption anisotropic layer 12 and the phase difference body 13 function as an anti-reflection film in the stack 2, from the perspective of highly achieving the anti-reflection function, the phase difference layer with an in-plane phase difference contained in the phase difference body preferably includes a λ / 4 phase difference layer having a λ / 4 plate function (i.e., a phase difference function of π / 2) in the entire visible light range. The λ / 4 phase difference layer is preferably a λ / 4 phase difference layer with reverse wavelength dispersion. As a phase difference layer with an in-plane phase difference, a phase difference layer formed by combining a phase difference layer (λ / 2 phase difference layer) with a λ / 2 plate function with positive wavelength dispersion and a λ / 4 phase difference layer with positive wavelength dispersion can also be used.

[0262] When the second light absorption anisotropic layer 12 and the phase difference body 13 function as an anti-reflection film, from the viewpoint of being able to compensate for the anti-reflection function in the inclined direction, the phase difference body may include a positive C plate as a phase difference layer having a phase difference in the thickness direction in addition to the phase difference layer having an in-plane phase difference.

[0263] When the phase difference body 13 includes a phase difference layer having an in-plane phase difference and a phase difference layer having a phase difference in the thickness direction, the stacking order thereof is not particularly limited, and the phase difference layer having an in-plane phase difference and the phase difference layer having a phase difference in the thickness direction may be sequentially provided from the second light absorption anisotropic layer 12 side, or the reverse order may be provided. A bonding layer may be provided between the phase difference layers constituting the phase difference body 13. The bonding layer is a pressure-sensitive adhesive layer or an adhesive layer.

[0264] The retardation body 13 preferably includes a first retardation layer (retardation layer) that satisfies the relationship of the following formula (4) and formula (5).

[0265] 120nm≤ReA(550)≤160nm (4)

[0266] ReA(450) / ReA(550)≤1.0 (5)

[0267] [In formula (4) and formula (5), ReA(λ) represents the in-plane retardation value of the first retardation layer at a wavelength of λ [nm].]

[0268] The ReA(550) of the first retardation layer may be 125 to 155, 130 to 150, or 135 to 145. When the ReA(550) of the first retardation layer is within the above range, the first retardation layer can function appropriately as a λ / 4 retardation layer.

[0269] If "ReA(450) / ReA(550)" in the above formula (5) is greater than 1.0, when the first phase difference layer and the second light absorption anisotropic layer 12 constitute an anti-reflection film (elliptically polarizing plate), the light leakage on the short wavelength side increases. "ReA(450) / ReA(550)" is preferably 0.7 to 1.0, more preferably 0.80 to 0.95, further preferably 0.80 to 0.92, and particularly preferably 0.82 to 0.88. As for the value of "ReA(450) / ReA(550)", when a polymerizable liquid crystal compound is used to obtain the first phase difference layer, it can be arbitrarily adjusted by adjusting the mixing ratio of the polymerizable liquid crystal compound.

[0270] The in-plane retardation value of the first retardation layer can be adjusted by the thickness of the first retardation layer. The in-plane retardation value can be determined by the following formula.

[0271] Re(λ)=d1×Δn(λ)

[0272] [Wherein,

[0273] Re(λ) represents the in-plane retardation value of the first retardation layer at a wavelength of λ [nm],

[0274] d1 represents the thickness of the first phase difference layer,

[0275] Δn(λ) represents the birefringence index of the first retardation layer at wavelength λ [nm].]

[0276] As understood from the above formula, in order to make the in-plane phase difference value (Re(λ)) at the wavelength λ[nm] of the first phase difference layer the desired value, it is sufficient to adjust Δn(λ) and thickness d1. The thickness of the first phase difference layer is preferably 0.5μm to 5μm, more preferably 1μm to 3μm. The thickness can be measured using an interference film thickness meter, a laser microscope or a stylus film thickness meter. It should be noted that when a polymerizable liquid crystal compound is used to obtain the first phase difference layer, Δn(λ) depends on the molecular structure of the polymerizable liquid crystal compound.

[0277] It is preferable that the first retardation layer further satisfies the relationship of the following formula (6).

[0278] TA(380)≤20 (6)

[0279] [In formula (6), TA(380) represents the transmittance [%] of the first retardation layer at a wavelength of 380 nm.]

[0280] The TA (380) of the first phase difference layer may be 15% or less, 10% or less, 8% or less, or 5% or less, and is usually 0.01% or more. By making the TA (380) of the first phase difference layer within the above range, even when the laminate including the first phase difference layer is laminated on the display element of the display device and the display device is exposed to the outdoors for a long time, the light-emitting layer of the display device can be protected from the influence of near-ultraviolet rays. Thus, the degradation of the light-emitting layer of the display device can be suppressed.

[0281] In addition, the TA (410) of the first phase difference layer may be less than 80%, less than 75%, or less than 70%. In addition, the TA (410) of the first phase difference layer may be less than 10%, less than 5%, and is usually greater than 0.01%. By making the TA (410) of the first phase difference layer within the above range, the degradation of the light-emitting layer of the display device can be further suppressed. TA (410) represents the transmittance [%] of the first phase difference layer at a wavelength of 410 nm.

[0282] As mentioned above, the phase difference body may include a phase difference layer having a phase difference in the thickness direction (hereinafter sometimes referred to as the "second phase difference layer"). The second phase difference layer is, for example, a positive C plate. The phase difference value Rth(550) in the thickness direction at a wavelength of 550nm of the positive C plate is usually in the range of greater than -170nm and less than -10nm, preferably in the range of greater than -150nm and less than -20nm, and more preferably in the range of greater than -100nm and -40nm. If the phase difference value in the thickness direction of the positive C plate is within this range, when the phase difference body and the second light absorption anisotropic layer 12 constitute an anti-reflection film (elliptically polarizing plate), the characteristic of preventing reflection from an oblique direction can be further improved. The phase difference value Rth(550) can be measured using a phase difference measuring device.

[0283] When the phase difference layers (first phase difference layer, second phase difference layer, etc.) constituting the phase difference body include a liquid crystal film, the phase difference layers can be incorporated into the laminate in a state of being laminated with a substrate layer (third substrate layer described later) supporting them. The phase difference layer and the substrate layer can be directly in contact.

[0284] The phase difference layer included in the phase difference body may be a stretched film or a liquid crystal film including a liquid crystal film, and is preferably a liquid crystal film.

[0285] When the phase difference layer is a stretched film, the stretched film can use a conventionally known stretched film, and can use a stretched film imparted with a phase difference by uniaxially stretching or biaxially stretching a resin film. As the resin film, cellulose films such as cellulose triacetate and cellulose diacetate, polyester films such as polyethylene terephthalate, polyethylene isophthalate and polybutylene terephthalate, acrylic resin films such as polymethyl (meth)acrylate and polyethyl (meth)acrylate, polycarbonate films, polyethersulfone films, polysulfone films, polyimide films, polyolefin films, polynorbornene films, etc. can be used, but are not limited thereto.

[0286] When the retardation layer is a stretched film, the thickness of the retardation layer is usually 5 μm to 200 μm, preferably 10 μm to 80 μm, and more preferably 40 μm or less.

[0287] When the retardation layer is a liquid crystal film, the liquid crystal film may include a liquid crystal film formed by applying a third composition including a compound having liquid crystallinity on a third base layer.

[0288] As the third substrate layer, the substrate layer described in the first substrate layer can be cited. The third substrate layer can be peeled off when incorporated into the laminate, or it can be used as a protective film for the phase difference layer without peeling off. As a liquid crystal compound, a liquid crystal compound having a polymerizable group, especially a photopolymerizable group, i.e., a polymerizable liquid crystal compound can be used. As a polymerizable liquid crystal compound, for example, a polymerizable liquid crystal compound previously known in the field of phase difference film can be used. The so-called photopolymerizable group refers to a group that can participate in the polymerization reaction using reactive species such as active free radicals, acids, etc. generated by a photopolymerization initiator. As a photopolymerizable group, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxypropyl, oxetane, etc. can be cited. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxypropyl and oxetane are preferred, and acryloyloxy is more preferred. Regarding liquid crystal properties, it can be thermotropic liquid crystal or lyotropic liquid crystal, but thermotropic liquid crystal is preferred from the perspective of being able to perform precise film thickness control. In addition, as a phase-ordered structure in thermotropic liquid crystal, it can be nematic liquid crystal or smectic liquid crystal. In addition, it can be rod-shaped liquid crystal or disc-shaped liquid crystal. The polymerizable liquid crystal compound can be used alone or in combination of two or more.

[0289] In the case where the first phase difference layer (λ / 4 phase difference layer) is a liquid crystal film comprising a liquid crystal cured film (liquid crystal film) obtained by polymerizing and curing a polymerizable liquid crystal compound, it is preferred that the polymerizable liquid crystal compound be oriented in the horizontal direction. As a polymerizable liquid crystal compound for obtaining the first phase difference layer, from the viewpoint of exhibiting reverse wavelength dispersion, it is preferably a liquid crystal having a T-shaped or H-shaped mesomorphic structure that further has birefringence in a direction perpendicular to the long axis direction of the molecule, and from the viewpoint of obtaining a stronger dispersion, a T-shaped liquid crystal is more preferred. As the structure of the T-shaped liquid crystal, specifically, for example, a compound represented by the following formula (II) can be cited.

[0290] [Chemical formula 5]

[0291]

[0292] [In formula (II),

[0293] Ar represents a divalent aromatic group which may have a substituent. Preferably, the divalent aromatic group contains at least one of a nitrogen atom, an oxygen atom, and a sulfur atom. When the number of aromatic groups contained in the divalent group Ar is two or more, the two or more aromatic groups may be bonded to each other through a divalent bonding group such as a single bond, -CO-O-, or -O-.

[0294] G 1 and G 2 Each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atoms contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group or a nitro group, and the carbon atoms constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted by an oxygen atom, a sulfur atom or a nitrogen atom.

[0295] L 1 , L 2 , B 1 and B 2 Each is independently a single bond or a divalent linking group.

[0296] k and l each independently represent an integer of 0 to 3 and satisfy the relationship 1≤k+1. Here, when 2≤k+1, B 1 and B 2 , G 1 and G 2 Each may be the same as or different from each other.

[0297] E 1 and E 2Each independently represents an alkanediyl group having 1 to 17 carbon atoms, wherein the hydrogen atom contained in the alkanediyl group may be substituted by a halogen atom, and the -CH2- contained in the alkanediyl group may be replaced by -O-, -S-, or -COO-. When there are multiple -O-, -S-, or -COO- groups, they are not adjacent to each other.

[0298] P 1 and P 2 Each independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.]

[0299] G 1 and G 2 Each independently preferably is a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms; more preferably is a 1,4-phenylenediyl group substituted with a methyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group; and particularly preferably is an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyl group.

[0300] In addition, it is preferred that there are multiple G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group, and more preferably 1 or L 2 Bonded G 1 and G 2 At least one of them is a divalent alicyclic hydrocarbon group.

[0301] L 1 and L 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -、-R a3 COOR a4 -、-R a5 OCOR a6 -、R a7 OC=OOR a8 -、-N=N-、-CR c =CR d -, or C≡C-. Here, R a1 ~R a8 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms, and R c and R d represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. 1 and L 2Each independently is more preferably a single bond, -O Ra2-1 -、-CH2-、-CH2CH2-、-COOR a4-1 -, or OCOR a6-1 -. Here, R a2-1 , R a4 -1 , R a6-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and L 2 Each independently is further preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or OCO-.

[0302] B 1 and B 2 Each of them is independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -、-R a11 COOR a12 -、-R a13 OCOR a14 -, or R a15 OC=OOR a16 -. Here, R a9 ~R a16 Each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. 1 and B 2 Each independently is more preferably a single bond, -OR a10-1 -、-CH2-、-CH2CH2-、-COOR a12-1 -, or OCOR a14-1 -. Here, R a10-1 , R a12-1 , R a14-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and B 2 Each independently is further preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or OCOCH2CH2-.

[0303] From the viewpoint of exhibiting reverse wavelength dispersion, k and l are preferably in the range of 2≤k+l≤6, preferably k+l=4, and more preferably k=2 and l=2. k=2 and l=2 are preferred because a symmetrical structure is obtained.

[0304] E 1 and E 2Each independently is preferably an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms.

[0305] As P 1 or P 2 The polymerizable group represented by , includes epoxy, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxirane and oxetanyl, etc. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxirane and oxetanyl are preferred, and acryloyloxy is more preferred.

[0306] Ar preferably has at least one selected from an aromatic hydrocarbon ring that may have a substituent, an aromatic heterocycle that may have a substituent, and an electron-withdrawing group. As the aromatic hydrocarbon ring, for example, a benzene ring, a naphthalene ring, an anthracene ring, etc. can be cited, preferably a benzene ring, a naphthalene ring. As the aromatic heterocycle, a furan ring, a benzofuran ring, a pyrrole ring, an indole ring, a thiophene ring, a benzothiophene ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a triazole ring, a triazine ring, a pyrroline ring, an imidazole ring, a pyrazole ring, a thiazole ring, a benzothiazole ring, a thienothiazole ring, an oxazole ring, a benzoxazole ring and a phenanthroline ring can be cited. Among them, preferably there is a thiazole ring, a benzothiazole ring or a benzofuran ring, and further preferably there is a benzothiazolyl group. In addition, when Ar contains a nitrogen atom, the nitrogen atom preferably has π electrons.

[0307] In formula (II), the total number Nπ of π electrons contained in the divalent aromatic group represented by Ar is preferably 8 or more, more preferably 10 or more, further preferably 14 or more, and particularly preferably 16 or more. It is preferably 30 or less, more preferably 26 or less, and further preferably 24 or less.

[0308] As the aromatic group represented by Ar, for example, the following groups are preferably mentioned.

[0309] [Chemical formula 6]

[0310]

[0311] [In formula (Ar-1) to formula (Ar-23),

[0312] The symbol * indicates a connection part.

[0313] Z 0 , Z 1 and Z 2Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms.

[0314] Q 1 and Q 2 Each independently represents -CR 2’ R 3’ -、-S-、-NH-、-NR 2’ -, -CO- or O-, R 2 ' and R 3’ Each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

[0315] J 1 and J 2 Each independently represents a carbon atom or a nitrogen atom.

[0316] Y 1 , Y 2 and Y 3 Each independently represents an aromatic hydrocarbon group or an aromatic heterocyclic group which may be substituted.

[0317] W 1 and W 2 Each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom.

[0318] m represents an integer from 0 to 6.]

[0319] As Y 1 , Y 2 and Y 3 The aromatic hydrocarbon group in the group includes an aromatic hydrocarbon group having 6 to 20 carbon atoms, such as phenyl, naphthyl, anthracenyl, phenanthrenyl, biphenyl, etc., preferably phenyl and naphthyl, more preferably phenyl. The aromatic heterocyclic group includes an aromatic heterocyclic group having 4 to 20 carbon atoms, such as furanyl, pyrrolyl, thienyl, pyridyl, thiazolyl, benzothiazolyl, etc., which contains at least one hetero atom such as nitrogen atom, oxygen atom, sulfur atom, etc., preferably furanyl, thienyl, pyridyl, thiazolyl, benzothiazolyl.

[0320] Y 1 , Y 2 and Y 3Each independently may be a substituted polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring collection. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring collection.

[0321] Z 0 , Z 1 and Z 2 Each of Z is independently preferably a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms. 0 More preferably, a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group. 1 and Z 2 More preferred are a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group and a cyano group.

[0322] Q 1 and Q 2 Preferred are -NH-, -S-, -NR 2’ -、-O-,R 2’ A hydrogen atom is preferred, and -S-, -O-, and -NH- are particularly preferred.

[0323] Among the compounds represented by formulae (Ar-1) to (Ar-23), compounds represented by formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.

[0324] In the compounds represented by formula (Ar-16) to (Ar-23), Y 1 The nitrogen atom and Z to which it can be bonded 0 Together, they form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include the aromatic heterocyclic rings that Ar may have and are described above, for example, a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, a pyrrolidine ring, etc. The aromatic heterocyclic group may have a substituent. In addition, Y 1 It can also be bonded to the nitrogen atom and Z 0 Together, they form the aforementioned optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group, for example, a benzofuran ring, a benzothiazole ring, a benzoxazole ring, and the like.

[0325] Among the polymerizable liquid crystal compounds, compounds with a maximum absorption wavelength of 300 to 400 nm are preferred. When a photopolymerization initiator is contained in the third composition containing the polymerizable liquid crystal compound, there is concern about the polymerization reaction and gelation of the polymerizable liquid crystal compound during long-term storage. However, when the maximum absorption wavelength of the polymerizable liquid crystal compound is 300 to 400 nm, even if it is exposed to ultraviolet light during storage, the generation of reactive species from the photopolymerization initiator and the polymerization reaction and gelation of the polymerizable liquid crystal compound caused by the reactive species can be effectively suppressed. Therefore, it is advantageous from the perspective of the long-term stability of the third composition, and the orientation and uniformity of the film thickness of the liquid crystal cured film contained in the first phase difference layer can be improved. It should be noted that the maximum absorption wavelength of the polymerizable liquid crystal compound can be measured using an ultraviolet-visible spectrophotometer in a solvent. The solvent is a solvent that can dissolve the polymerizable liquid crystal compound, and chloroform and the like can be cited as examples.

[0326] Relative to 100 parts by mass of the solid content of the third composition, the content of the polymerizable liquid crystal compound in the third composition is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and further preferably 90 to 95 parts by mass. When the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the perspective of the orientation of the obtained liquid crystal cured film. It should be noted that the so-called solid content of the third composition refers to all components after removing volatile components such as organic solvents from the third composition.

[0327] The phase difference layer (the first phase difference layer or the second phase difference layer) as a liquid crystal film may further include a third orientation layer in addition to the liquid crystal film. The third orientation layer can be selected according to the direction in which the liquid crystal compound is oriented, and may be a vertical orientation layer or a horizontal orientation layer. When the third orientation layer is a material that serves as an orientation control force to make it present a horizontal orientation, the liquid crystal compound can form a horizontal orientation or a mixed orientation, and when it is a material that makes it present a vertical orientation, the liquid crystal compound can form a vertical orientation or an inclined orientation. Expressions such as horizontal and vertical indicate the direction of the long axis of the oriented liquid crystal compound when the plane of the phase difference layer is used as a reference. For example, the so-called vertical orientation refers to the long axis of the liquid crystal compound oriented in a direction perpendicular to the plane of the phase difference layer. The so-called vertical here refers to 90°±20° relative to the plane of the phase difference layer. As the third orientation layer, the orientation layers described in the first orientation layer and the second orientation layer can be cited.

[0328] When the phase difference layer (the first phase difference layer or the second phase difference layer) serving as a liquid crystal film absorbs light in the ultraviolet region, the combination of the phase difference layer with the first UV absorption layer and the second UV absorption layer can further help suppress the degradation of display elements of an organic EL light-emitting display device.

[0329] On the other hand, the phase difference layer (first phase difference layer or second phase difference layer) as a liquid crystal film is not only degraded by ultraviolet rays, but also tends to degrade under short-wavelength visible light according to the maximum absorption wavelength of the polymerizable liquid crystal compound. Therefore, in the laminate 2 obtained by combining the above-mentioned phase difference layer with the first UV absorption layer or the second UV absorption layer satisfying the relationship of formula (3), the degradation of the above-mentioned phase difference layer caused by short-wavelength visible light can be suppressed.

[0330] The thickness of the liquid crystal film is preferably 0.5 μm to 5 μm, and more preferably 1 μm to 3 μm.

[0331] (Lamination layer)

[0332] The laminating layer is an adhesive layer or a pressure-sensitive adhesive layer.

[0333] When the laminating layer is an adhesive layer, it is an adhesive layer formed using an adhesive composition. The adhesive composition or the reaction product of the adhesive composition is a substance that exhibits adhesiveness by attaching itself to an adherend, and is called a so-called pressure-sensitive adhesive. In addition, the adhesive layer formed using the active energy ray-curable adhesive composition described later can adjust the degree of crosslinking and the adhesive force by irradiating active energy rays.

[0334] As adhesive composition, adhesives with excellent optical transparency known in the past can be used without particular limitation, for example, adhesive compositions containing base polymers such as acrylic polymers, carbamate polymers, silicone polymers, polyvinyl ethers can be used. In addition, adhesive composition can be active energy ray curing adhesive composition or heat curing adhesive composition etc. Among them, adhesive compositions using acrylic resins excellent in transparency, adhesion, re-peelability (reoperability), weatherability, heat resistance etc. as base polymers are preferred. The adhesive layer is preferably composed of the reaction product of the adhesive composition comprising (meth) acrylic resin, crosslinking agent, silane compound, and may also include other components.

[0335] The adhesive composition for forming the adhesive layer can include base polymers such as acrylic polymers, urethane polymers, silicone polymers, polyvinyl ethers, etc. The adhesive composition can be an active energy ray-curable adhesive, a thermosetting adhesive, etc. Among them, an adhesive using a (meth) acrylic resin having excellent transparency, adhesion, re-peelability (re-operability), weather resistance, heat resistance, etc. as a base polymer is preferred. The adhesive layer is preferably composed of a reaction product of an adhesive comprising a (meth) acrylic resin, a crosslinking agent, and a silane compound, and may also include other components.

[0336] The adhesive layer can be formed using an active energy ray-curable adhesive. For active energy ray-curable adhesives, a harder adhesive layer can be formed by adding an ultraviolet curable compound such as a multifunctional acrylate to the above-mentioned adhesive composition and curing it by irradiating ultraviolet rays after forming the adhesive layer. Active energy ray-curable adhesives have the property of being cured by irradiation with energy rays such as ultraviolet rays and electron beams. Active energy ray-curable adhesives also have adhesiveness before energy ray irradiation, and therefore have the property of being able to fit closely to an adherend, being cured by irradiation with energy rays, and adjusting the adhesion.

[0337] The thickness of the adhesive layer is not particularly limited, and is usually 5 μm to 300 μm, 10 μm to 250 μm, 15 μm to 100 μm, or 20 μm to 50 μm.

[0338] When the laminating layer is an adhesive layer, the adhesive layer can be formed using an adhesive composition. The adhesive composition used to form the adhesive layer is an adhesive other than a pressure-sensitive adhesive (adhesive), for example, a water-based adhesive, an active energy ray-curable adhesive.

[0339] Examples of the water-based adhesive include an adhesive obtained by dissolving or dispersing a polyvinyl alcohol resin in water. The drying method when using the water-based adhesive is not particularly limited, and for example, a method of drying using a hot air dryer or an infrared dryer may be used.

[0340] Examples of active energy ray-curable adhesives include solvent-free active energy ray-curable adhesives containing curable compounds that are cured by irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays. By using solvent-free active energy ray-curable adhesives, interlayer adhesion can be improved.

[0341] When the bonding layer is an adhesive layer, the thickness is preferably 0.1 μm or more, and may be 0.5 μm or more, and is preferably 10 μm or less, and may be 5 μm or less.

[0342] (Organic EL display device)

[0343] The organic EL display device is a display device in which the above-mentioned laminated body is laminated on a display element via an adhesive layer. In the organic EL display device, the laminated body is incorporated so that the first UV absorbing layer side becomes the viewing side.

[0344] The display elements of the organic EL display device have weak resistance to light in the ultraviolet region and also degrade under short-wavelength visible light. The hue is easily changed when displaying white (when emitting light). However, in the organic EL display device having the above-mentioned stacked body, the hue change when displaying white can be suppressed.

[0345] Example

[0346] The present invention will be described in more detail below by showing Examples and Comparative Examples, but the present invention is not limited to these Examples. Unless otherwise specified, "%" and "part" in Examples and Comparative Examples are mass % and mass parts.

[0347] [Preparation of base material layer]

[0348] (Substrate layer (1): TAC film)

[0349] As the substrate layer (1), a triacetyl cellulose (TAC) film (KC4UY-TAC, manufactured by Konica Minolta Co., Ltd.) was prepared. The substrate layer (1) was a film containing an ultraviolet absorber.

[0350] (Base layer (2): PET film)

[0351] As the base material layer (2), a polyethylene terephthalate (PET) film (Diafoil T140E25, manufactured by Mitsubishi Plastics Co., Ltd.) was prepared. The thickness of the base material layer (2) was 38 μm.

[0352] (Base layer (3): COP film / HC layer)

[0353] A cycloolefin polymer (COP) film (G+, manufactured by Zeon Co., Ltd., Japan) was subjected to corona treatment. A hard coat forming composition (ARONIX (registered trademark) UV3701, manufactured by Toagosei Co., Ltd.) was applied to the corona treated surface of the COP film by gravure coating to form a coating layer. The coating layer on the COP film was dried at 100°C for 3 minutes and then irradiated with a high pressure mercury lamp at a cumulative light intensity of 500 mJ / cm 2 The substrate layer (3) is prepared by irradiating ultraviolet rays under conditions of , to form a hard coating (HC) layer with a thickness of 2 μm. The substrate layer (3) has a layer structure of COP film / HC layer. The COP film is a film containing an ultraviolet absorber.

[0354] (Base material layer (4): UV-HC layer / COP film)

[0355] 70 parts of multifunctional acrylate ("A-DPH-12E": manufactured by Shin-Nakamura Chemical Industry Co., Ltd.), 30 parts of urethane acrylate ("UV-7650B": manufactured by Nippon Chemical Industry Co., Ltd.), 3 parts of polymerization initiator ("NCI-730": manufactured by ADEKA Co., Ltd.), 2 parts of a compound represented by the following formula (UVA-04), and 34 parts of methyl ethyl ketone were mixed to prepare a hard coat layer-forming composition containing an ultraviolet absorber (hereinafter sometimes referred to as a "UV-HC layer-forming composition"). The compound represented by formula (UVA-04) was synthesized with reference to the description of Synthesis Example 4 of Japanese Patent Publication No. 2017-120430.

[0356] [Chemical formula 7]

[0357]

[0358] Next, a corona treatment was applied to one side of a COP film (G+, manufactured by Zeon Co., Ltd., Japan), and a UV-HC layer-forming composition was applied using a bar coater to form a coating layer. Dry air at a temperature of 70°C was circulated for 30 seconds at a flow rate of 0.5 m / s to the coating layer on the COP film to evaporate the solvent, and the accumulated light intensity was 200 mJ / cm 2 The substrate layer (4) is prepared by irradiating the substrate with ultraviolet rays in a manner to form a hard coating layer containing an ultraviolet absorber (hereinafter sometimes referred to as a "UV-HC layer") with a thickness of 5 μm. The substrate layer (4) has a layer structure of a UV-HC layer / COP film.

[0359] (Base material layer (5): UV-HC layer / COP film / HC layer)

[0360] The substrate layer (3) (COP film / HC layer) is produced by the above steps. The COP film surface of the produced substrate layer (3) is subjected to corona treatment, and a UV-HC layer is formed on the substrate layer (3) by the step of forming a UV-HC layer described in the substrate layer (4), thereby producing a substrate layer (5). The substrate layer (5) has a layer structure of UV-HC layer / COP film / HC layer.

[0361] (Base material layer (6): COP film)

[0362] As the substrate layer (6), a cycloolefin polymer (COP) film (ZF-14-50, manufactured by Zeon Corporation of Japan) was prepared. The substrate layer (6) was a film having no ultraviolet absorption capability.

[0363] [Preparation of polarizing plate]

[0364] (Preparation of the Second Light Absorption Anisotropic Layer (1))

[0365] A polyvinyl alcohol resin film having an average degree of polymerization of about 2,400 and a saponification degree of 99.9 mol % or more and having a thickness of 30 μm was immersed in pure water at a temperature of 30° C., and then immersed in an aqueous solution having a weight ratio of iodine / potassium iodide / water of 0.02 / 2 / 100 at a temperature of 30° C. to perform iodine dyeing (iodine dyeing step). The polyvinyl alcohol resin film having undergone the iodine dyeing step was immersed in an aqueous solution having a weight ratio of potassium iodide / boric acid / water of 12 / 5 / 100 at a temperature of 56.5° C. to perform boric acid treatment (boric acid treatment step). The polyvinyl alcohol resin film having undergone the boric acid treatment step was washed with pure water at a temperature of 8° C., and then dried at a temperature of 65° C., to obtain a second light absorption anisotropic layer (1) as a polarizer (thickness after stretching) in which iodine was adsorbed and oriented on the polyvinyl alcohol resin film. At this time, stretching was performed in the iodine dyeing step and the boric acid treatment step. The total stretching ratio in the stretching was 5.3 times.

[0366] (Preparation of water-based adhesive)

[0367] To 100 parts of water were added 3 parts of carboxyl-modified polyvinyl alcohol (KURARAY POVAL KL318, manufactured by KURARAY) and 1.5 parts of a water-soluble polyamide epoxy resin (Sumirez resin 650 (aqueous solution having a solid content concentration of 30%), manufactured by Sumika Chemtex) to prepare a water-based adhesive.

[0368] (Production of Polarizing Plate (1))

[0369] The substrate layer (1) prepared above is used as a protective film. The second light absorption anisotropic layer (polarizer) prepared above and the saponified substrate layer (1) are bonded together via the above-mentioned aqueous adhesive using a clamping roller. While applying tension to the obtained bonded product, it is dried at a temperature of 60°C for 2 minutes to obtain a polarizing plate (1) having a substrate layer (1) on one side of the second light absorption anisotropic layer (1). The polarizing plate (1) has a layer structure of substrate layer (1) / adhesive layer / second light absorption anisotropic layer (1).

[0370] The optical properties of the polarizing plate (1) were measured using a spectrophotometer (V7100, manufactured by JASCO Corporation) with the second light absorption anisotropic layer (1) of the polarizing plate (1) as the incident surface. The results showed that the visibility-corrected single transmittance was 42.7% and the visibility-corrected polarization degree was 99.991%.

[0371] (Production of Polarizing Plate (2))

[0372] The substrate layer (4) (UV-HC layer / COP film) prepared above is used as a protective film, and the COP film surface of the substrate layer (4) is subjected to a corona treatment. The corona-treated surface of the substrate layer (4) is bonded to the second light-absorbing anisotropic layer (1) prepared above via the above-mentioned aqueous adhesive using a clamping roller. While applying tension to the obtained bonded product, it is dried at a temperature of 60°C for 2 minutes to obtain a polarizing plate (2). The polarizing plate (2) has a layer structure of substrate layer (4) (UV-HC layer / COP film) / adhesive layer / second light-absorbing anisotropic layer (1).

[0373] The optical properties of the polarizing plate (2) were measured using a spectrophotometer (V7100, manufactured by JASCO Corporation) with the second light absorption anisotropic layer (1) of the polarizing plate (2) as the incident surface. The results showed that the visibility-corrected single transmittance was 42.5% and the visibility-corrected polarization degree was 99.990%.

[0374] (Production of Polarizing Plate (3))

[0375] The substrate layer (6) prepared above is used as a protective film, and one side of the substrate layer (6) is subjected to a corona treatment. Using a clamping roller, the corona-treated surface of the protective film is bonded to the second light-absorbing anisotropic layer (1) prepared above via the above-mentioned water-based adhesive. While applying tension to the obtained bonded product, it is dried at a temperature of 60°C for 2 minutes to obtain a polarizing plate (3). The polarizing plate (3) has a layer structure of substrate layer (6) / adhesive layer / second light-absorbing anisotropic layer (1). The substrate layer (6) is a film that does not have ultraviolet absorption ability.

[0376] The optical properties of the polarizing plate (3) were measured using a spectrophotometer (V7100, manufactured by JASCO Corporation) with the second light absorption anisotropic layer (1) surface of the polarizing plate (3) as the incident surface. The results showed that the visibility-corrected single transmittance was 42.4% and the visibility-corrected polarization degree was 99.990%.

[0377] (Production of polarizing plate (4))

[0378] Using the substrate layer (3) prepared above as a protective film, the HC layer side of the substrate layer (3) is subjected to corona treatment. Using a clamping roller, the corona-treated surface of the protective film is bonded to the second light-absorbing anisotropic layer (1) prepared above via the above-mentioned water-based adhesive. While applying tension to the obtained bonded product, it is dried at a temperature of 60°C for 2 minutes to obtain a polarizing plate (4). The polarizing plate (4) has a layer structure of substrate layer (3) (COP film / HC layer) / adhesive layer / second light-absorbing anisotropic layer (1). The COP film of the substrate layer (3) is a film containing a UV absorber. The optical properties of the polarizing plate (4) were measured using a spectrophotometer (V7100, manufactured by JASCO Corporation) with the second light absorption anisotropic layer (1) of the polarizing plate (4) as the incident surface. The results showed that the visibility-corrected single transmittance of the polarizing plate was 42.1%, and the visibility-corrected polarization degree was 99.991%.

[0379] [Preparation of the first phase difference layer]

[0380] (Production of the first phase difference layer (1))

[0381] 5 parts of a photo-alignment material having the structure shown below (weight average molecular weight: 30,000) and 95 parts of cyclopentanone (solvent) were mixed, and the obtained mixture was stirred at 80° C. for 1 hour to prepare a composition for forming a horizontal alignment layer.

[0382] [Chemical formula 8]

[0383]

[0384] The polymerizable liquid crystal compound (1) and the polymerizable liquid crystal compound (2) having the structures shown below were prepared respectively. The polymerizable liquid crystal compound (1) was prepared according to the method described in Japanese Patent Application Publication No. 2010-31223. The polymerizable liquid crystal compound (2) was prepared according to the method described in Japanese Patent Application Publication No. 2009-173893.

[0385] Polymerizable liquid crystal compound (1):

[0386] [Chemical formula 9]

[0387]

[0388] Polymerizable liquid crystal compound (2):

[0389] [Chemical formula 10]

[0390]

[0391] 1 mg of the polymerizable liquid crystal compound (1) was dissolved in 50 mL of tetrahydrofuran to obtain a solution. The obtained solution was placed in a measuring cuvette with an optical path length of 1 cm as a measuring sample, and the measuring sample was placed in an ultraviolet visible spectrophotometer (UV-2450, manufactured by Shimadzu Corporation), and the absorption spectrum was measured. The wavelength of maximum absorbance was read from the obtained absorption spectrum, and the maximum absorption wavelength λmax in the range of 300 to 400 nm was 350 nm.

[0392] A polymerizable liquid crystal compound (1) and a polymerizable liquid crystal compound (2) are mixed in a mass ratio of 90:10 to obtain a mixture. 0.1 parts of a leveling agent (BYK-361N, manufactured by BM Chemie) and 6 parts of 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butane-1-one (Irgacure (registered trademark) 369 (Irg369), manufactured by BASF Japan Co., Ltd.) as a photopolymerization initiator are added to 100 parts of the obtained mixture. Furthermore, N-methyl-2-pyrrolidone (NMP) is added in such a manner that the solid content concentration becomes 13%. The mixture is stirred at a temperature of 80°C for 1 hour to prepare a third composition (1) for forming a liquid crystal film.

[0393] After the substrate layer (6) was subjected to corona treatment, the horizontal alignment layer forming composition prepared above was applied using a bar coater, dried at 80°C for 1 minute, and irradiated with a polarized UV light device (SPOT CURE SP-9, manufactured by USHIO INC.) at a wavelength of 313 nm with a cumulative light intensity of 100 mJ / cm 2 Polarized UV light exposure was performed under the conditions of to form a horizontal alignment layer. The thickness of the horizontal alignment layer was measured by an ellipsometer and the result was 200 nm.

[0394] Next, the third composition (1) prepared above was coated on the horizontal alignment layer using a bar coater, and after heating at 120° C. for 60 seconds, ultraviolet rays (in a nitrogen atmosphere, cumulative light intensity at a wavelength of 365 nm: 500 mJ / cm ) were irradiated from the surface coated with the third composition (1) using a high-pressure mercury lamp (Unicure VB-15201BY-A, manufactured by USHIO INC.). 2 ), thereby forming a liquid crystal film (liquid crystal cured film) as a cured layer of a polymerizable liquid crystal compound, and forming a first retardation layer (1) having a layer structure of a horizontal alignment layer and a liquid crystal cured film. Thus, a first retardation layer with a substrate having a layer structure of a substrate layer (6) / first retardation layer (1) (horizontal alignment layer / liquid crystal cured film) is obtained.

[0395] After confirming that the substrate layer (6) has no phase difference, the in-plane phase difference values ​​of the first phase difference layer with the substrate at a wavelength of 450 nm and a wavelength of 550 nm were measured using a phase difference measuring device (KOBRA-WPR, manufactured by Oji Instruments Co., Ltd.), and the in-plane phase difference values ​​ReA(450) and ReA(550) of the first phase difference layer at a wavelength of 450 nm and a wavelength of 550 nm were calculated. As a result, ReA(550) of the first phase difference layer was 142 nm, and ReA(450) / ReA(550) was 0.85.

[0396] (Production of the first phase difference layer (2))

[0397] An unstretched film made of a norbornene-based resin having a glass transition temperature (Tg) of 125° C. was uniaxially stretched in the transverse direction in an atmosphere at a temperature of 128° C. to obtain a stretched film as the first retardation layer ( 2 ). The uniaxial stretching was performed using a tenter-type stretching machine.

[0398] The in-plane retardation values ​​ReA(450) and ReA(550) of the first retardation layer (2) were measured using a retardation measuring device (KOBRA-WPR, manufactured by Oji Instruments Co., Ltd.). As a result, the in-plane retardation Re(550) was 140 nm, the in-plane retardation Re(450) was 142 nm, and ReA(450) / ReA(550) was 1.01. The direction of the slow axis of the first retardation layer (2) was parallel to the stretching direction of the stretched film.

[0399] [Preparation of the second phase difference layer]

[0400] To 100 parts of Paliocolor LC242 (polymerizable liquid crystal compound, manufactured by BASF), 0.1 parts of F-556 as a leveling agent and 3 parts of Irga cure 369 as a polymerization initiator were added. Cyclopentanone was added so that the solid content concentration became 13% to obtain a third composition (2).

[0401] The substrate layer (6) was cut into a quadrilateral and subjected to a corona treatment once under the conditions of an output of 0.3 kW and a treatment speed of 3 m / min using a corona treatment device (AGF-B10, manufactured by Kasuga Electric Co., Ltd.). The third composition (2) was applied to the corona-treated surface of the substrate layer (6) using a bar coater, and then dried in a drying oven set to 100° C. for 1 minute. Next, ultraviolet rays (under a nitrogen atmosphere, wavelength: 365 nm, cumulative light intensity at a wavelength of 365 nm: 500 mJ / cm) were irradiated using a high-pressure mercury lamp (Unicure VB-15201BY-A, manufactured by USHIO INC.). 2), thereby forming a second phase difference layer in which the polymerizable liquid crystal compound is vertically oriented relative to the coating plane. Thus, a second phase difference layer with a substrate having a layer structure of substrate layer (6) / second phase difference layer is obtained.

[0402] In order to confirm the orientation state of the polymerizable liquid crystal compound in the second phase difference layer, after confirming that the substrate layer (6) has no phase difference, a phase difference measuring device (KOBRA-WPR, manufactured by Prince Instruments Co., Ltd.) is used to measure the phase difference value Rth in the thickness direction of the second phase difference layer. In the measurement, the incident angle of light to the second phase difference layer is changed, and the front phase difference value and the phase difference value when tilted 40° around the fast axis are measured. The average refractive index at each wavelength is measured using an ellipsometer M-220 manufactured by JASCO Corporation. In addition, the thickness of the coating film of the vertically oriented phase difference layer is measured using an Optical NanoGauge film thickness meter C12562-01 (manufactured by Hamamatsu Photonics Co., Ltd.).

[0403] The three-dimensional refractive index was calculated based on the measured front phase difference value, the phase difference value when tilted 40° around the fast axis, the average refractive index, and the thickness of the second phase difference layer, with reference to the Oji Instruments technical data (https: / / oji-keisoku.co.jp / support / download / index.php). Based on the obtained three-dimensional refractive index, the phase difference value Rth(λ) in the thickness direction at the wavelength λ[nm] of the second phase difference layer was calculated according to the following formula.

[0404] Rth(λ)

[0405] =((nx(λ)+ny(λ)) / 2-nz(λ))×d2

[0406] [Wherein,

[0407] nx(λ) represents the principal refractive index at a wavelength λ nm in the plane of the second retardation layer.

[0408] Ny(λ) represents a refractive index at a wavelength λ [nm] in the same plane as nx(λ) and in a direction perpendicular to nx(λ).

[0409] nz(λ) represents the refractive index of the second retardation layer at a wavelength λ [nm] in the thickness direction,

[0410] When nx(λ)=ny(λ), nx(λ) can be set to a refractive index in an arbitrary direction within the plane of the second retardation layer.

[0411] d2 represents the thickness of the second phase difference layer.]

[0412] As a result, Rth(550) of the second retardation layer was -70 nm, and RthC(450) / RthC(550) was 1.10.

[0413] [Preparation of Adhesive Layer (1)]

[0414] As the adhesive layer (1), an acrylic pressure-sensitive adhesive having a thickness of 20 μm (manufactured by LINTEC) was prepared.

[0415] [Preparation of Adhesive Layer (2)]

[0416] With reference to the description of Production Example 6 of JP-A-2017-120430, an adhesive composition and an adhesive sheet were prepared. The adhesive sheet is a sheet having an adhesive layer (2) containing a compound represented by formula (UVA-04) on the release-treated surface of the separator.

[0417] [Example 1]

[0418] (Preparation of the first composition (1))

[0419] The following components were mixed and stirred at 80° C. for 1 hour to obtain a first composition (1).

[0420] Polymerizable liquid crystal compound (3): 75 parts

[0421] Polymerizable liquid crystal compound (4): 25 parts

[0422] Dichroic pigment (1): 1 part

[0423] Polymerization initiator (Irgacure 369, manufactured by BASF): 6 parts

[0424] Non-liquid crystal compound having a polymerizable group (dipentaerythritol hexaacrylate (6-functional)): 1.5 parts

[0425] Leveling agent (F-556, manufactured by DIC Corporation): 0.25 parts

[0426] Solvent (o-xylene): 300 parts

[0427] The polymerizable liquid crystal compounds (3) and (4) have the structures shown below and were synthesized according to the method described in Lub et al., Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996).

[0428] Polymerizable liquid crystal compound (3):

[0429] [Chemical formula 11]

[0430]

[0431] ·Polymerizable liquid crystal compound (4):

[0432] [Chemical formula 12]

[0433]

[0434] The dichroic dye (1) used was an azo dye described in Examples of JP-A-2013-101328 having the structure shown below: The maximum absorption wavelength of the dichroic dye (1) measured in a chloroform solution was 600 nm.

[0435] Dichroic pigments (1):

[0436] [Chemical formula 13]

[0437]

[0438] (Preparation of the First Light Absorption Anisotropic Layer (a) with Substrate)

[0439] The substrate layer (1) prepared above was cut into a quadrilateral and subjected to a corona treatment once under the conditions of an output of 0.3 kW and a treatment speed of 3 m / min using a corona treatment device (AGF-B10, manufactured by Kasuga Electric Co., Ltd.). The first composition (1) was applied to the corona-treated surface of the cut substrate layer (1) using a bar coater, and then dried in a drying oven set to 100° C. for 1 minute. Next, ultraviolet rays (under a nitrogen atmosphere, wavelength: 365 nm, cumulative light intensity at a wavelength of 365 nm: 500 mJ / cm) were irradiated using a high-pressure mercury lamp (Unicure VB-15201BY-A, manufactured by USHIO INC.). 2 ), thereby forming a first light absorption anisotropic layer (1) in which the polymerizable liquid crystal compound and the dichroic dye are vertically oriented relative to the coating plane. Thus, a first light absorption anisotropic layer (a) with a substrate having a layer structure of substrate layer (1) / first light absorption anisotropic layer (1) is obtained.

[0440] (Production of Laminated Body (1))

[0441] The first light absorption anisotropic layer (a) with a substrate, the polarizing plate (1), and the first phase difference layer with a substrate prepared above are used, and the first light absorption anisotropic layer (1), the substrate layer (1) constituting the polarizing plate (1), and the first phase difference layer (1) (the surface on the liquid crystal cured film side) are subjected to corona treatment, and they are stacked via the adhesive layer (1) prepared above to obtain a laminate (1). The laminate (1) has a layer structure of substrate layer (1) (first UV absorbing layer) / first light absorption anisotropic layer (1) / adhesive layer (1) / substrate layer (1) (second UV absorbing layer) / adhesive layer / second light absorption anisotropic layer (1) / adhesive layer (1) / first phase difference layer (1) (liquid crystal cured film / horizontal alignment layer) / substrate layer (6). In the laminate (1), the angle formed by the absorption axis of the second light absorption anisotropic layer and the slow axis of the first retardation layer (1) is 45°.

[0442] [Example 2]

[0443] (Preparation of the First Light Absorption Anisotropic Layer (b) with Substrate)

[0444] A first light absorption anisotropic layer (b) with a substrate having a layer structure of substrate layer (5) (UV-HC layer / COP film / HC layer) / first light absorption anisotropic layer (1) is obtained by following the steps for preparing a first light absorption anisotropic layer (a) with a substrate, except that a substrate layer (5) is used instead of a substrate layer (1), the HC layer side of the substrate layer (5) is corona treated, and the first composition (1) is coated on the corona treated surface.

[0445] (Production of Laminated Body (2))

[0446] A laminate (2) is obtained according to the steps of preparing the laminate (1), except that the first light absorption anisotropic layer (b) with a substrate is used instead of the first light absorption anisotropic layer (a) with a substrate. The laminate (2) has a layer structure of substrate layer (5) (UV-HC layer / COP film / HC layer) / first light absorption anisotropic layer (1) / adhesive layer (1) / substrate layer (1) (second UV absorption layer) / adhesive layer / second light absorption anisotropic layer (1) / adhesive layer (1) / first phase difference layer (1) (liquid crystal cured film / horizontal alignment layer) / substrate layer (6). The substrate layer (5) is the first UV absorption layer.

[0447] [Example 3]

[0448] (Production of Laminated Body (3))

[0449] A laminate (3) is obtained by following the steps of preparing the laminate (1), except that the polarizing plate (2) is used instead of the polarizing plate (1). The laminate (3) has a layer structure of substrate layer (1) (first UV absorbing layer) / first light absorbing anisotropic layer (1) / adhesive layer (1) / substrate layer (4) (UV-HC layer / COP film) / adhesive layer / second light absorbing anisotropic layer (1) / adhesive layer (1) / first phase difference layer (1) (liquid crystal cured film / horizontal alignment layer) / substrate layer (6). The substrate layer (4) is the second UV absorbing layer.

[0450] [Example 4]

[0451] (Production of Laminated Body (4))

[0452] A laminate (4) is obtained by following the steps of preparing the laminate (3), except that the first phase difference layer (2) is used instead of the first phase difference layer with a substrate. The laminate (4) has a layer structure of substrate layer (1) (first UV absorbing layer) / first light absorbing anisotropic layer (1) / adhesive layer (1) / substrate layer (4) (UV-HC layer / COP film) / adhesive layer / second light absorbing anisotropic layer (1) / adhesive layer (1) / first phase difference layer (2). The substrate layer (4) is the second UV absorbing layer.

[0453] [Example 5]

[0454] (Preparation of the First Light Absorption Anisotropic Layer (c) with Substrate)

[0455] A first light absorption anisotropic layer (c) with a substrate having a layer structure of substrate layer (3) (COP film / HC layer) / first light absorption anisotropic layer (1) is obtained by following the steps for preparing a first light absorption anisotropic layer (a) with a substrate, except that a substrate layer (3) is used instead of a substrate layer (1), the HC layer side of the substrate layer (3) is corona treated, and the first composition (1) is coated on the corona treated surface.

[0456] (Production of Laminated Body (5))

[0457] A laminate (5) is obtained according to the steps of preparing the laminate (3), except that the first light absorption anisotropic layer (c) with a substrate is used instead of the first light absorption anisotropic layer (a) with a substrate. The laminate (5) has a layer structure of substrate layer (3) (COP film / HC layer) / first light absorption anisotropic layer (1) / adhesive layer (1) / substrate layer (4) (UV-HC layer / COP film) / adhesive layer / second light absorption anisotropic layer (1) / adhesive layer (1) / first phase difference layer (1) (liquid crystal cured film / horizontal alignment layer) / substrate layer (6). The substrate layer (3) is the first UV absorption layer, and the substrate layer (4) is the second UV absorption layer.

[0458] [Example 6]

[0459] (Production of Laminated Body (6))

[0460] The substrate layer (6) is peeled off from the laminate (5) prepared by the above steps, and the second phase difference layer side of the second phase difference layer with the substrate is bonded via the adhesive layer (1) prepared above to obtain a laminate (6). The laminate (6) has a layer structure of substrate layer (3) (COP film / HC layer) / first light absorption anisotropic layer (1) / adhesive layer (1) / substrate layer (4) (UV-HC layer / COP film) / adhesive layer / second light absorption anisotropic layer (1) / adhesive layer (1) / first phase difference layer (1) (liquid crystal cured film / horizontal alignment layer) / adhesive layer (1) / second phase difference layer / substrate layer (6). The substrate layer (4) is the second UV absorption layer.

[0461] [Example 7]

[0462] A laminate (7) is obtained according to the steps of preparing the laminate (6), except that the first light absorption anisotropic layer (b) with a substrate is used instead of the first light absorption anisotropic layer (c) with a substrate. The laminate (7) has a layer structure of substrate layer (5) (UV-HC layer / COP film / HC layer) / first light absorption anisotropic layer (1) / adhesive layer (1) / substrate layer (4) (UV-HC layer / COP film) / adhesive layer / second light absorption anisotropic layer (1) / adhesive layer (1) / first phase difference layer (1) (liquid crystal cured film / horizontal alignment layer) / adhesive layer (1) / second phase difference layer / substrate layer (6). The substrate layer (5) is the first UV absorption layer, and the substrate layer (4) is the second UV absorption layer.

[0463] [Example 8]

[0464] (Preparation of the first composition (2))

[0465] The following components were mixed and stirred at 80° C. for 1 hour to obtain a first composition (2).

[0466] Polymerizable liquid crystal compound (3): 75 parts

[0467] Polymerizable liquid crystal compound (4): 25 parts

[0468] Dichroic pigment (1): 1 part

[0469] Dichroic pigment (2): 1 part

[0470] Polymerization initiator (Irgacure 369, manufactured by BASF): 6 parts

[0471] Non-liquid crystal compound having a polymerizable group (dipentaerythritol hexaacrylate (6-functional)): 1.5 parts

[0472] Leveling agent (F-556, manufactured by DIC Corporation): 0.25 parts

[0473] Solvent (o-xylene): 300 parts

[0474] The dichroic dye (2) used was an azo dye described in Examples of JP-A-2013-101328 having the structure shown below: The maximum absorption wavelength of the dichroic dye (2) measured in a chloroform solution was 488 nm.

[0475] Dichroic pigments (2):

[0476] [Chemical formula 14]

[0477]

[0478] (Preparation of the First Light Absorption Anisotropic Layer (d) with Substrate)

[0479] A first light absorption anisotropic layer (d) with a substrate having a layer structure of substrate layer (3) (COP film / HC layer) / first light absorption anisotropic layer (2) is obtained by following the steps for producing a first light absorption anisotropic layer (1) with a substrate, except that a substrate layer (3) is used instead of a substrate layer (1), a first composition (2) is used instead of the first composition (1), the HC layer side of the substrate layer (3) is corona treated, and the first composition (2) is coated on the corona treated surface.

[0480] (Production of Laminated Body (8))

[0481] A laminate (8) is obtained according to the steps of preparing the laminate (7), except that the first light absorption anisotropic layer (d) with a substrate is used instead of the first light absorption anisotropic layer (b) with a substrate. The laminate (8) has a layer structure of substrate layer (3) (COP film / HC layer) / first light absorption anisotropic layer (2) / adhesive layer (1) / substrate layer (4) (UV-HC layer / COP film) / adhesive layer / second light absorption anisotropic layer (1) / adhesive layer (1) / first phase difference layer (1) (liquid crystal cured film / horizontal alignment layer) / adhesive layer (1) / second phase difference layer / substrate layer (6). The substrate layer (3) is the first UV absorption layer, and the substrate layer (4) is the second UV absorption layer.

[0482] [Example 9]

[0483] A laminate (9) is prepared according to the steps for preparing a laminate (1), except that the first light absorbing anisotropic layer (1) of the first light absorbing anisotropic layer (a) with a substrate is bonded to the substrate layer (1) of the polarizing plate (1) using an adhesive layer (2). The laminate (9) has a layer structure of substrate layer (1) (first UV absorbing layer) / first light absorbing anisotropic layer (1) / adhesive layer (2) / substrate layer (1) / adhesive layer / second light absorbing anisotropic layer (1) / adhesive layer (1) / first phase difference layer (1) (liquid crystal cured film / horizontal alignment layer) / substrate layer (6). The substrate layer (1) is the first UV absorbing layer, and the adhesive layer (2) and the substrate layer (1) are the second UV absorbing layer.

[0484] [Example 10]

[0485] (Preparation of the First Light Absorption Anisotropic Layer (e) with Substrate)

[0486] A first light absorption anisotropic layer (e) with a substrate having a layer structure of substrate layer (5) (UV-HC layer / COP film / HC layer) / first light absorption anisotropic layer (2) is obtained by following the steps for producing a first light absorption anisotropic layer (a) with a substrate, except that a substrate layer (5) is used instead of a substrate layer (1), a first composition (2) is used instead of the first composition (1), the HC layer side of the substrate layer (5) is subjected to corona treatment, and the first composition (2) is coated on the corona treated surface.

[0487] A laminate (10) is prepared according to the steps of preparing the laminate (7), except that the first light absorption anisotropic layer (e) with a substrate is used instead of the first light absorption anisotropic layer (b) with a substrate, and the polarizing plate (4) is used instead of the polarizing plate (2). The laminate (10) has a layer structure of substrate layer (5) (UV-HC layer / COP film / HC layer) / first light absorption anisotropic layer (2) / adhesive layer (1) / substrate layer (3) (COP film / HC layer) / adhesive layer / second light absorption anisotropic layer (1) / adhesive layer (1) / first phase difference layer (1) (liquid crystal cured film / horizontal alignment layer) / adhesive layer (1) / second phase difference layer / substrate layer (6). The substrate layer (5) is the first UV absorption layer, and the substrate layer (3) is the second UV absorption layer.

[0488] [Comparative Example 1]

[0489] (Preparation of Alignment Layer Forming Composition)

[0490] To 0.3 parts of oriented polymer SUNEVER (registered trademark) SE-610 (manufactured by Nissan Chemical Industries, Ltd.) (solid content concentration 1.0%), 27.7 parts of propylene glycol monomethyl ether was added to obtain an oriented layer forming composition. The solid content concentration of the oriented polymer was calculated from the concentration described in the delivery specification.

[0491] (Preparation of the first composition (3))

[0492] The following components were mixed and stirred at 80° C. for 1 hour to obtain a first composition (3).

[0493] Polymerizable liquid crystal compound (3): 75 parts

[0494] Polymerizable liquid crystal compound (4): 25 parts

[0495] Dichroic pigment (1): 2.8 parts

[0496] Polymerization initiator (Irgacure 369, manufactured by BASF): 6 parts

[0497] Leveling agent (BYK-361N (polyacrylate compound), manufactured by BYK-Chemie): 0.3 parts

[0498] Solvent (o-xylene): 300 parts

[0499] (Preparation of the First Light Absorption Anisotropic Layer (f) with Substrate)

[0500] The substrate layer (2) was cut into a quadrilateral and subjected to one corona treatment under the conditions of an output power of 0.3 kW and a treatment speed of 3 m / min using a corona treatment device (AGF-B10, manufactured by Kasuga Electric Co., Ltd.). After coating the composition for forming an orientation layer on the corona-treated surface of the substrate layer (2) using a rod coater, the composition was dried in a drying oven set to 120°C for 1 minute to obtain an orientation layer. Further, the first composition (3) was coated on the obtained orientation layer using a rod coater, and the composition was dried in a drying oven set to 100°C for 1 minute. Next, a high-pressure mercury lamp (Unicure VB-15201BY-A, manufactured by USHIO INC.) was used to irradiate with ultraviolet rays (under a nitrogen atmosphere, wavelength: 365 nm, cumulative light intensity at a wavelength of 365 nm: 1000 mJ / cm 2 ), thereby forming a first light absorption anisotropic layer (3) in which the polymerizable liquid crystal compound and the dichroic dye are vertically oriented relative to the coating film plane. Thus, a light absorption anisotropic layer (f) with a substrate having a layer structure of substrate layer (2) / orientation layer / first light absorption anisotropic layer (3) is obtained.

[0501] (Production of Laminated Body (11))

[0502] The first light absorption anisotropic layer (f) with a substrate, the polarizing plate (1), and the first phase difference layer with a substrate prepared above are used, and the first light absorption anisotropic layer (3) and the first phase difference layer (1) (the surface on the liquid crystal cured film side) are subjected to corona treatment, and they are stacked via the adhesive layer (1) prepared above to obtain a laminate (11). The laminate (11) has a layer structure of substrate layer (2) / orientation layer / first light absorption anisotropic layer (3) / adhesive layer (1) / substrate layer (1) (second UV absorption layer) / adhesive layer / second light absorption anisotropic layer (1) / adhesive layer (1) / first phase difference layer (1) (liquid crystal cured film / horizontal orientation layer) / substrate layer (6). In the laminate (11), the angle between the absorption axis of the second light absorption anisotropic layer and the slow axis of the first phase difference layer (1) is 45°.

[0503] [Comparative Example 2]

[0504] (Preparation of the First Light Absorption Anisotropic Layer (g) with Substrate)

[0505] A first light absorbing anisotropic layer (g) with a substrate having a layer structure of substrate layer (2) / orientation layer / light absorbing anisotropic layer (1) is prepared according to the steps for preparing a first light absorbing anisotropic layer (f) with a substrate, except that the first composition (1) is used instead of the first composition (3).

[0506] (Production of Laminated Body (10))

[0507] A laminate (12) is obtained according to the steps of preparing the laminate (11), except that the first light absorption anisotropic layer with substrate (g) prepared above is used instead of the first light absorption anisotropic layer with substrate (f), and the polarizing plate (3) is used instead of the polarizing plate (1). The laminate (12) has a layer structure of substrate layer (2) / alignment layer / first light absorption anisotropic layer (1) / adhesive layer (1) / substrate layer (6) / adhesive layer / second light absorption anisotropic layer (1) / adhesive layer (1) / first phase difference layer (1) (liquid crystal cured film / horizontal alignment layer) / substrate layer (6).

[0508] [Comparative Example 3]

[0509] A laminate (13) is obtained by following the steps of preparing the laminate (12), except that the polarizing plate (1) is used instead of the polarizing plate (3). The laminate (13) has a layer structure of substrate layer (2) / orientation layer / first light absorption anisotropic layer (1) / adhesive layer (1) / substrate layer (1) / adhesive layer / second light absorption anisotropic layer (1) / adhesive layer (1) / first phase difference layer (1) (liquid crystal cured film / horizontal orientation layer) / substrate layer (6).

[0510] [Comparative Example 4]

[0511] A laminate (14) is obtained by following the steps for preparing the laminate (12) except that the first light absorption anisotropic layer with substrate (a) prepared above is used instead of the first light absorption anisotropic layer with substrate (g). The laminate (14) has a layer structure of substrate layer (1) / first light absorption anisotropic layer (1) / adhesive layer (1) / substrate layer (6) / adhesive layer / second light absorption anisotropic layer (1) / adhesive layer (1) / first phase difference layer (1) (liquid crystal cured film / horizontal alignment layer) / substrate layer (6).

[0512] [Measurement of Phase Transition Temperature of Polymerizable Liquid Crystal Compound]

[0513] The phase transition temperature was confirmed by observing the texture of the polymerizable liquid crystal compound on the glass substrate having the alignment layer formed thereon using a polarizing microscope (BX-51, manufactured by Olympus Corporation) while heating the polymerizable liquid crystal compound.

[0514] The polymerizable liquid crystal compound (3) exhibited a smectic A phase from a crystalline phase at 95°C when the temperature was raised, phase-changed to a nematic phase at 111°C, and phase-changed to an isotropic liquid phase at 113°C. When the temperature was lowered, it was confirmed that the phase changed to a nematic phase at 112°C, the phase changed to a smectic A phase at 110°C, and the phase changed to a smectic B phase at 94°C.

[0515] The polymerizable liquid crystal compound (4) exhibited a smectic A phase from a crystalline phase at 81°C when the temperature was raised, phase-changed to a nematic phase at 121°C, and phase-changed to an isotropic liquid phase at 137°C. When the temperature was lowered, it was confirmed that the phase changed to a nematic phase at 133°C, phase-changed to a smectic A phase at 118°C, and phase-changed to a smectic B phase at 78°C.

[0516] As a reference, the texture of thermotropic nematic liquid crystal LC242 manufactured by BASF and polymerizable liquid crystal compound (1) were observed in the same manner. These showed only a nematic phase, and no clear smectic phase.

[0517] [Measurement of absorbance of first light absorption anisotropic layer]

[0518] (Preparation of the First Light Absorption Anisotropic Layer)

[0519] The first light absorption anisotropic layer (1) was formed on the substrate layer (6) according to the procedure for preparing the first light absorption anisotropic layer (a) with a substrate, except that the substrate layer (6) was used instead of the substrate layer (1). The surface of the substrate layer (6) on the side of the first light absorption anisotropic layer (1) was bonded to a glass having a size of 4 cm×4 cm and a thickness of 0.7 mm via the adhesive layer prepared above, to prepare a measurement sample (1). The measurement samples (2) and (3) were prepared in the same manner as the preparation of the measurement sample (1), except that the first compositions (2) and (3) were used instead of the first composition (1).

[0520] (Determination of absorbance)

[0521] The prepared measurement sample in the above text was placed in an ultraviolet-visible spectrophotometer (UV-2450, manufactured by Shimadzu Corporation), and the absorbance was measured. The absorbances Ax, Ay, Ax(z = 30°), Ax(z = 60°), Ay(z = 30°), and Ay(z = 60°) at the maximum absorption wavelength (λmax) in the range from wavelength 410 nm to wavelength 780 nm were measured. During the measurement, the measurement sample was placed in the above ultraviolet-visible spectrophotometer, and after calibration so that the absorbance at wavelength 800 nm became zero, Ax was measured. For Ax(z = 30°), Ax(z = 60°), Ay(z = 30°), and Ay(z = 60°), they were also measured in the state where the measurement sample was tilted by 30° or 60° after calibration so that the absorbance at wavelength 800 nm became zero. Ax and Ax(z = 60°) are as described in the above formulas (3) and (7). In addition, for Ay, Ax(z = 30°), Ay(z = 30°), and Ay(z = 60°), they are as described in the method for the absorbance Az of the calculation formula (2). The results are shown in Tables 1 to 3.

[0522] The satisfaction of the relationship of the above formula (2) is judged by the following steps.

[0523] In the state where the measurement sample was rotated by 30° and 60° in a manner including the y-axis, the same linearly polarized light as when measuring Ax was incident, thereby measuring Ax(z = 30°) and Ax(z = 60°). Similarly, in the state where the measurement sample was rotated by 30° and 60° in a manner including the x-axis, the same linearly polarized light as when measuring Ay was incident, thereby measuring Ay(z = 30°) and Ay(z = 60°).

[0524] In the case where there is no absorption anisotropy in the x-y plane, that is, when Ax is equal to Ay, Ax(z = 30°) = Ay(z = 30°) and Ax(z = 60°) = Ay(z = 60°). Therefore, Ax(z = 30°) and Ay(z = 30°) are denoted as A(z = 30°), Ax(z = 60°) and Ay(z = 60°) are denoted as A(z = 60), and Ax(z = 90°) and Ay(z = 90°) are denoted as A(z = 90).

[0525] In the case where the relationship of A(z = 30°) < A(z = 60°) holds, the relationship of A(z = 30°) < A(z = 60°) < A(z = 90°) = Az holds. Therefore, if A(z = 30°) > (Ax + Ay) / 2 or A(z = 60°) > (Ax + Ay) / 2, it is judged that the relationship of the above formula (2) is satisfied.

[0526] [Measurement of Thickness of First Light Absorption Anisotropic Layer]

[0527] The thickness of the first light absorption anisotropic layer was measured using an ellipsometer (M-220 manufactured by JASCO Corporation).

[0528] [Transmittance measurement]

[0529] The transmission spectrum was measured using a spectrophotometer (UV-2450, manufactured by Shimadzu Corporation) by incident light from the normal direction on the film surface of the measurement object. For the adhesive layer (2), the measurement was performed as an integral product bonded to the substrate layer. The transmission spectrum was measured with a step size of 2 nm for light ranging from a wavelength of 380 nm to a wavelength of 780 nm. The transmittance was determined from the obtained transmission spectrum. The results are shown in Tables 1 to 3.

[0530] [Appearance evaluation of laminate (1)]

[0531] (Evaluation of initial laminate appearance (1))

[0532] The substrate layer (6) of the laminate prepared above was peeled off and adhered to an alkali-free glass having a thickness of 0.7 mm via the adhesive layer (1) prepared above to prepare an evaluation sample. The front glass and polarizing plate were removed from the "Galaxy S5" manufactured by SAMSUNG, and the display device was taken out. The evaluation sample was loaded through water on the taken-out display device in such a way that the first light absorption anisotropic layer side became the viewing side compared to the second light absorption anisotropic layer. Then, the power of the display device was turned on (ON), and all settings for changing the screen display color such as the blue light cutoff function and the color balance change were turned off (OFF) on the basis of maximizing the brightness. In the state where a white screen was displayed (the state where the HTML color code #FFFFFF was displayed), the hue observed from the front and the hue observed from the oblique direction during the white display were confirmed. The hue and hue difference in each direction at this time were evaluated according to the evaluation criteria shown below, and this was used as the initial evaluation. The results are shown in Tables 1 to 3.

[0533] <Evaluation Criteria>

[0534] A: There is almost no noticeable hue difference.

[0535] B: The hue from the front or the hue from the oblique direction is slightly perceived, but the hue difference between the front and oblique directions is hardly perceived.

[0536] C: The hue from the front or the hue from the oblique direction is slightly perceived, but the hue difference between the front and oblique directions is not much perceived.

[0537] D: The hue difference is felt.

[0538] E: The hue difference is strongly felt.

[0539] (Appearance Evaluation of Laminated Body after Light Resistance Test (1))

[0540] The display device using the evaluation sample was placed in a light resistance tester (SUNTEST XLS+, manufactured by ATLAS) with the first light absorption anisotropic layer on the upper side relative to the second light absorption anisotropic layer, and the light intensity was adjusted to 288400 kJ / m 2 The display device after the light resistance test was irradiated with light under the conditions of . The hue when the white display was observed from the front and the hue when the white display was observed from the oblique direction were confirmed by the steps described in the initial evaluation of the appearance of the laminated body (1). The hue and hue difference in each direction at this time were evaluated according to the evaluation criteria shown below, and this was used as the evaluation after the light resistance test. The results are shown in Tables 1 to 3.

[0541] <Evaluation Criteria>

[0542] A: There is almost no noticeable hue difference.

[0543] B: The hue from the front or the hue from the oblique direction is slightly perceived, but the hue difference between the front and oblique directions is hardly perceived.

[0544] C: A slight change in the color tone from the front or from the oblique direction compared to the initial stage is perceived, but the hue difference between the front and oblique directions is not perceived much.

[0545] D: A hue difference is felt, and a difference from the initial color tone is felt.

[0546] E: The hue difference is strongly felt, and the difference from the initial color tone is strongly felt.

[0547] [Appearance evaluation of laminate (2)]

[0548] (Evaluation of initial laminate appearance (2))

[0549] The substrate layer (6) of the laminate prepared above is peeled off and attached to an alkali-free glass with a thickness of 0.7 mm via the adhesive layer (1) prepared above to prepare an evaluation sample. The front glass and polarizing plate are removed from the "Galaxy S5" manufactured by SAMSUNG, and the display device is taken out. On the taken-out display device, the evaluation sample is loaded through water in such a way that the first light absorption anisotropic layer side becomes the viewing side compared to the second light absorption anisotropic layer. Then, when the power of the display device is turned off (OFF) (when black is displayed), the color tone of the reflected hue when viewed from the front direction and the oblique direction is confirmed, and evaluated according to the evaluation criteria shown below, which is used as the initial evaluation. The results are shown in Tables 1 to 3.

[0550] <Evaluation Criteria>

[0551] A: The hue is barely perceptible.

[0552] B: The color tone is slightly felt.

[0553] C: Feel the hue.

[0554] D: The hue is strongly felt.

[0555] (Appearance Evaluation of Laminated Body after Light Resistance Test (2))

[0556] The display device using the evaluation sample was placed in a light resistance tester (SUNTEST XLS+, manufactured by ATLAS) with the first light absorption anisotropic layer on the upper side relative to the second light absorption anisotropic layer, and the light intensity was adjusted to 288400 kJ / m 2 The display device after the light resistance test was irradiated with light under the conditions of . For the display device after the light resistance test, the color tone of the reflected hue was confirmed by the steps described in the initial appearance evaluation of the laminate (2), and the evaluation was performed according to the evaluation criteria shown below, which was used as the evaluation after the light resistance test. The results are shown in Tables 1 to 3.

[0557] A: The hue is barely perceptible.

[0558] B: The color tone is slightly felt.

[0559] C: Feel the hue.

[0560] D: The color tone is strongly felt, and the difference from the initial reflected hue is also felt.

[0561] [Table 1]

[0562]

[0563] [Table 2]

[0564]

[0565] [Table 3]

[0566]

[0567] Description of Reference Numerals

[0568] 1, 2 laminated body, 11 first light absorption anisotropic layer, 12 second light absorption anisotropic layer, 13 phase difference body, 21 first ultraviolet absorption layer (first UV absorption layer), 22 second ultraviolet absorption layer (second UV absorption layer).

Claims

1. A laminate comprising, in this order, a first ultraviolet absorbing layer, a first light absorbing anisotropic layer, a second ultraviolet absorbing layer, and a second light absorbing anisotropic layer, The first light absorption anisotropic layer is formed of a composition including one or more dichroic pigments and a liquid crystal compound. The second light absorption anisotropic layer has an absorption axis in a direction parallel to the plane thereof. The first ultraviolet absorbing layer and the second ultraviolet absorbing layer both satisfy the relationship of the following formula (1): The first light absorption anisotropic layer satisfies the following relationship (2): T(380)≤20 (1) Az>(Ax+Ay) / 2 (2) In formula (1), T(380) represents the transmittance [%] at a wavelength of 380 nm. In formula (2), Ax, Ay and Az are the absorbances of the first light absorption anisotropic layer at the maximum absorption wavelength within the wavelength range of 410 nm to 780 nm, and respectively represent the absorbances of linearly polarized light vibrating along the x-axis direction, the y-axis direction and the z-axis direction, in, The x-axis is a direction parallel to the absorption axis direction of the second light-absorbing anisotropic layer in the plane of the first light-absorbing anisotropic layer. The y-axis is a direction orthogonal to the x-axis in the plane of the first light-absorbing anisotropic layer. The z-axis is a direction orthogonal to the x-axis and the y-axis.

2. The laminate according to claim 1, wherein At least one of the first ultraviolet absorbing layer and the second ultraviolet absorbing layer satisfies the relationship of the following formula (3): T(410)≤20 (3) In formula (3), T(410) represents the transmittance [%] at a wavelength of 410 nm.

3. The laminate according to claim 2, wherein: The second ultraviolet absorbing layer satisfies the relationship of the formula (3).

4. The laminate according to any one of claims 1 to 3, wherein The liquid crystal compound can form a smectic liquid crystal phase.

5. The laminate according to claim 1 or 2, wherein: The second light absorption anisotropic layer further comprises a retardation layer satisfying the relationship of the following formula (4) and formula (5) on the side opposite to the second ultraviolet absorption layer side. The phase difference layer is a cured layer of a polymerizable liquid crystal compound. 120nm≤ReA(550)≤160nm (4) ReA(450) / ReA(550)≤1.0 (5) In the formula (4) and the formula (5), ReA(λ) represents the in-plane retardation value of the retardation layer at a wavelength λ [nm].

6. The laminate according to claim 5, wherein: The phase difference layer satisfies the following formula (6): TA(380)≤20 (6) In formula (6), TA(380) represents the transmittance [%] of the retardation layer at a wavelength of 380 nm.

7. The laminate according to claim 1 or 2, wherein: The dichroic pigment is an azo compound.

8. The laminate according to claim 1 or 2, wherein: The first light absorption anisotropic layer satisfies the following relationship between equations (7) and (8): Ax(z=60°) / Ax≥5 (7) Ay(z=60°) / Ay≥5 (8) In formula (7), Ax(z=60°) is the absorbance of the maximum absorption wavelength of the first light absorption anisotropic layer, and represents the absorbance of linearly polarized light vibrating along the x-axis direction when the first light absorption anisotropic layer is rotated 60° with the y-axis as the rotation axis. In formula (8), Ay(z=60°) is the absorbance of the maximum absorption wavelength of the first light absorption anisotropic layer, and represents the absorbance of linearly polarized light vibrating along the y-axis direction when the first light absorption anisotropic layer is rotated 60° about the x-axis.

9. The laminate according to claim 1 or 2, wherein: The second ultraviolet absorbing layer satisfies the following relationship (9): 80nm≤ReB(550)≤160nm (9) In the formula (9), ReB(550) represents the in-plane retardation value of the second ultraviolet absorbing layer at a wavelength of 550 nm.

10. An organic EL display device, wherein: The laminate according to claim 1 or 2 is laminated on a display element via an adhesive layer.

Citation Information

Patent Citations

  • Silver halide photographic sensitive material and its development processing method

    JP1992330434A

  • Compound, optical film, and manufacturing method for optical film

    JP2009173893A

  • Compound, optical film, and method for producing optical film

    JP2010031223A

  • Light absorption anisotropic film, production method thereof, and liquid crystal display device using the same

    JP2011237513A

  • Polarizing film, circularly polarizing plate and their manufacturing method

    JP2013101328A